Polyethylene resin composition, molded article and container
A tailored polyethylene resin composition with specific ethylene polymers and optimized catalysts addresses impact strength and fluidity issues, ensuring high moldability and resistance to environmental stress cracking in injection stretch blow molding.
Patent Information
- Application Number
- JP2021009421
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-09
- Filing Date
- 2021-01-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-01-25
AI Technical Summary
Existing polyethylene resin compositions for injection stretch blow molding exhibit insufficient impact strength, fluidity, and environmental stress cracking resistance, leading to issues such as high resin temperature during extrusion and shortened molding cycles.
A polyethylene resin composition comprising specific amounts of ethylene homopolymers and copolymers with α-olefins, characterized by defined melt flow rates, densities, molecular weights, and branch number indices, optimized using metallocene catalysts to enhance compatibility and balance rigidity, impact resistance, and environmental stress cracking resistance.
The composition achieves improved moldability, excellent balance of rigidity and impact resistance, and high compatibility of resin components, reducing molding defects and enhancing the appearance of injection stretch blow molded products.
Smart Images

Figure 0007604911000003 
Figure 0007604911000004 
Figure 0007604911000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyethylene resin composition, and a molded article and a container containing the polyethylene resin composition. [Background technology]
[0002] In the hollow molding, injection molding, inflation molding, and extrusion molding of polyethylene, materials with good moldability and physical properties are generally required. In particular, polyethylene resins with excellent moldability, physical properties, and chemical properties are widely used for hollow bottles that are generally used as containers for cosmetics, detergents, shampoos, and conditioners, or food containers for edible oils, etc. In recent years, there has been a notable trend toward shortening molding cycles to improve productivity, and toward thinner, lighter containers to reduce costs and the environmental impact. This has created a demand for materials that have a better balance of formability, rigidity, environmental stress crack resistance, and impact strength.
[0003] In the field of blow molding, particularly in the field of injection stretch blow containers, various materials exhibiting good mechanical properties, thermal properties, chemical resistance, etc. have been investigated, and polyolefins, particularly polyethylene resins, are widely used.
[0004] For example, Patent Document 1 describes a densitometer having a density of 0.940 to 0.968 g / cm 3 Disclosed is a polyethylene-based resin for injection stretch blow molding, which is characterized by containing an ethylene homopolymer, an ethylene-α-olefin copolymer, or a blend thereof, having an MFR of 0.3 to 10 g / 10 min and a flow ratio of 15 or more and less than 30, and which has excellent surface gloss and surface smoothness in addition to general properties such as impact strength and rigidity. However, the polyethylene resin described in Patent Document 1 has a density of 0.940 to 0.968 g / cm, which is obtained by a low pressure process using a Ziegler catalyst or a medium pressure process such as a Phillips process. 3 High density polyethylene, or density 0.925g / cm 3This is a polyethylene resin that contains the following high-pressure polyethylene as one component, and its physical properties such as impact strength may be insufficient.
[0005] Patent Document 2 discloses a container having a uniform thickness and excellent uniform gloss and cleanability throughout the entire container, the container being obtained by injection stretch blow molding an ethylene homopolymer or a copolymer of ethylene and an α-olefin having the following characteristics (A) to (E): (A) Melt index (MI) at 190°C under a load of 2.16 kg 2.16 ) is 0.5-10g / 10min (B) Molecular weight distribution measured by gel permeation chromatography is 3-6 (C) Density is 0.935 g / cm 3 End (D) Viscosity (η) at 200°C and a shear rate of 0.1 rad / s 0.1 ) from 1,000 Pa.s to 20,000 Pa.s (E) Viscosity (η) at 200°C and a shear rate of 100 rad / s 100 ) from 300 Pa.s to 2,000 Pa.s. However, the polymer described in Patent Document 2 is obtained by polymerizing ethylene alone or copolymerizing ethylene with an α-olefin having 3 to 20 carbon atoms in a slurry state using a supported catalyst prepared from (a) a support substance, (b) an organoaluminum compound, (c) a borate compound having active hydrogen, and (d) a titanium compound bonded with a cyclopentadienyl or substituted cyclopentadienyl group by η-bonding. Therefore, the physical properties such as impact strength may be insufficient.
[0006] Patent Document 3 also describes a polymer having (A) a melt index of 1 to 15 g / 10 min at 190° C. under a load of 2.16 kg, (B) a flow ratio of 10 to 14.5, and (C) a density of 0.961 to 0.973 g / cm. 3 This disclosure discloses a high-density polyethylene resin for injection stretch blow molding, which is capable of being stretch-blow molded at a high draw ratio and has excellent surface gloss and buckling strength for the molded bottles. However, the high-density polyethylene resin described in Patent Document 3 is an ethylene polymer prepared using a specific Ziegler catalyst, a chromium catalyst, a specific metallocene catalyst, or the like, and may have insufficient physical properties such as impact strength.
[0007] Patent Document 4 discloses an injection stretch blow molded (ISBM) article containing an HDPE resin that exhibits an MI2 of 0.1 to 5.0 dg / min when measured at 190°C / 2.16 kg according to ASTM D-1238, a density of 0.940-0.970 g / cc when measured according to ASTM D792, a peak molecular weight of 40,000 g / mol or more, and a zero shear viscosity in the range of 15,000 to 250,000 Pa·s. However, even this HDPE resin may have insufficient physical properties such as impact strength.
[0008] Therefore, the applicant has found polyethylene materials and the like having a high crystallization rate that can achieve even higher speed molding and high cycle while having blow moldability, high rigidity, impact resistance, etc., and has previously filed patent applications (Patent Documents 5 to 11).Patent Documents 5 to 7 disclose polyethylene resin compositions for containers that are polymerized with 60 to 90% by mass of a specific polyethylene using a metallocene catalyst containing Ti, Zr or Hf, have specific values for HLMFR and density, contain 10 to 40% by mass of a specific ethylene polymer having a long chain branching structure, and satisfy specific properties. Patent Documents 8 to 10 disclose polyethylene resin compositions that contain specific amounts of three specific types of polyethylene components and that satisfy the properties (1) to (5). Property (1): MFR is 0.1 to 1 g / 10 min. Property (2): HLMFR is 10 to 50 g / 10 min. Characteristic (3): HLMFR / MFR is 50~140. Property (4): Density is 0.940 to 0.965 g / cm 3 It is. Property (5): In a log-log plot of the extensional viscosity η(t) (unit: Pa·sec) measured at a temperature of 170°C and an extensional strain rate of 0.1 (unit: 1 / sec) versus the extensional time t (unit: sec), an inflection point in the extensional viscosity due to strain hardening is observed. Furthermore, Patent Document 11 discloses a polyethylene resin composition that contains 5% by mass or more and 40% by mass or less of a specific polyethylene component (A) and 60% by mass or more and 95% by mass or less of a specific polyethylene component (B) and satisfies the following properties (1) to (4): Property (1): MFR is 0.1 g / 10 min or more and 1 g / 10 min or less. Property (2): HLMFR is 10g / 10min or more and 50g / 10min or less. Property (3): The melt flow rate ratio (HLMFR / MFR), which is the ratio of HLMFR to MFR, is 40 or more and 140 or less. Property (4): Density is 0.950g / cm 3 More than 0.970g / cm 3 The following is the result. However, although the polyethylene resin compositions described in Patent Documents 5 to 11 all produce molded articles with high impact resistance, they have low fluidity and the resin temperature is likely to become high during the extrusion process, so there are still problems in shortening the entire molding cycle. In addition, the applicant has disclosed in Patent Document 12 that the density (D) is 0.900 to 0.975 g / cm 3 and discloses an ethylene polymer composition for thin-walled containers, which contains 10 to 90% by weight of an ethylene polymer (D) having a melt flow rate (MFR(D), measured in accordance with JIS K7210 at a temperature of 190°C and a load of 2.16 kg) of 0.05 to 1,000 g / 10 min, and 90 to 10% by weight of an ethylene polymer (C) obtained by multistage polymerization of a component (A) and a component (B), each having a specific density and HLMFR. The ethylene polymer disclosed in Patent Document 12 is said to be excellent in moldability, durability, and impact strength, and is less likely to cause unevenness derived from high molecular weight gel, allowing the production of molded articles with excellent appearance. However, the performance requirements for products are increasing day by day, and higher impact resistance than that of the ethylene polymer of Patent Document 12 is required, and further performance improvements are required to address the problems of the above-mentioned conventional techniques. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 9-194534 [Patent Document 2] Japanese Patent Application Publication No. 11-171923 [Patent Document 3] JP 2000-86722 A [Patent Document 4] Special Publication No. 2017-520477 [Patent Document 5] JP 2013-204015 A [Patent Document 6] JP 2014-208749 A [Patent Document 7] JP 2014-208750 A [Patent Document 8] JP 2017-179256 A [Patent Document 9] JP 2017-179294 A [Patent Document 10] JP 2018-131571 A [Patent Document 11] JP 2017-186515 A [Patent Document 12] JP 2016-55871 A Summary of the Invention [Problem to be solved by the invention]
[0010] In view of the above-mentioned problems in the prior art, an object of the present invention is to provide a polyethylene resin composition which has good moldability in injection stretch blow molding, an excellent balance of the rigidity, environmental stress crack resistance, and impact resistance of a molded article, has high compatibility with resin components, and provides an excellent appearance of the molded article, and to provide a molded article and a container using the same. [Means for solving the problem]
[0011] Means for Solving the Problems The present inventors have conducted intensive research to solve the above-mentioned problems and have found that a polyethylene resin composition containing specific polyethylene components (A) and (B) in specific amounts and satisfying specific properties can provide a polyethylene resin composition which has an excellent balance of injection stretch blow moldability, rigidity of a molded article, environmental stress crack resistance, and impact resistance, and which has high compatibility of the resin components, and which also provides a molded article made therefrom. This finding led to the completion of the present invention.
[0012] The polyethylene resin composition of the present invention comprises, as an essential component, one or more ethylene polymers selected from the group consisting of ethylene homopolymers and copolymers of ethylene with an α-olefin having 3 to 12 carbon atoms, and contains 15% by mass or more and 40% by mass or less of the following polyethylene component (A) and 60% by mass or more and 85% by mass or less of the following polyethylene component (B), and satisfies the following properties (1) to (6): Polyethylene component (A); Property (a1): The high melt flow rate (HLMFR) at a temperature of 190° C. and a load of 21.6 kg is 0.7 g / 10 min or more and 10.0 g / 10 min or less; Property (a2): Density is 0.915g / cm 3 More than 0.945g / cm 3 Polyethylene, which is: Polyethylene component (B); Property (b1): A melt flow rate (MFR) at a temperature of 190° C. and a load of 2.16 kg is 5.0 g / 10 min or more and 50.0 g / 10 min or less; Characteristics (b2): Density is 0.950g / cm 3 More than 0.980g / cm3 Polyethylene, which is: Property (1): MFR is greater than 1.0 g / 10 min and less than or equal to 5.0 g / 10 min. Property (2): HLMFR is 30 g / 10 min or more and 300 g / 10 min or less. Property (3): The melt flow rate ratio (HLMFR / MFR), which is the ratio of HLMFR to MFR, is 10 or more and 60 or less. Property (4): Density is 0.940g / cm 3 More than 0.965g / cm 3 The following is the result. Property (5): The number average molecular weight (Mn) measured by gel permeation chromatography (GPC) is 8,600 or more, and the weight average molecular weight (Mw) is 91,000 or more. Property (6): The branching index, calculated by the following formula using the number of branches per 1,000 carbon atoms of each component at molecular weights of 50,000, 100,000, 200,000, 300,000 and 400,000 as measured by GPC-IR, is 2.34 or more. [Branch count index] = [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 50,000] x [X 5万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 100,000] × [X 10万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 200,000] × [X 20万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 300,000] × [X 30万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 400,000] × [X 40万 ] Where: [X 5万 ] = [weight fraction of molecular weight 50,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 10万 ] = [weight fraction of molecular weight 100,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 20万] = [weight fraction of molecular weight 200,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 30万 ] = [weight fraction of molecular weight 300,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 40万 ] = [weight fraction of molecular weight 400,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000 and 400,000] [Sum of weight fractions of molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000] = [(weight fraction of molecular weight of 50,000) + (weight fraction of molecular weight of 100,000) + (weight fraction of molecular weight of 200,000) + (weight fraction of molecular weight of 300,000) + (weight fraction of molecular weight of 400,000)]
[0013] Moreover, the polyethylene resin composition of the present invention preferably further satisfies the following properties (7) and (8) from the viewpoint of impact resistance. Property (7): Tensile impact strength is 130kJ / m 2 That's all. Property (8): Tensile impact strength (TIS) (unit: kJ / m 2 ) and HLMFR (unit: g / 10 min) satisfy the relationship represented by the following formula (1). TIS≧1560×HLMFR -0.55 ·Formula (1)
[0014] The molded article of the present invention is a molded article produced using the polyethylene resin composition of the present invention.
[0015] The container of the present invention is a container produced using the polyethylene resin composition of the present invention. Effect of the Invention
[0016] Effects of the Invention According to the present invention, there is achieved an effect of providing a polyethylene resin composition which has good moldability in injection stretch blow molding of polyethylene, and which provides a molded article with an excellent balance of rigidity, environmental stress crack resistance, and impact resistance, and which has high compatibility with resin components and provides a molded article with an excellent appearance, and a molded article and a container using the same. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a typical plot of extensional viscosity, illustrating a case where an inflection point of extensional viscosity is observed. [Diagram 2] FIG. 2 is a typical plot of extensional viscosity, illustrating a case where an inflection point of the extensional viscosity is not observed. [Diagram 3] FIG. 3 is a graph showing the relationship between the HLMFR and the tensile impact strength (TIS) of the polyethylene resin compositions of the Examples and Comparative Examples. [Figure 4] FIG. 4 is a graph showing the relationship between the HLMFR and the melt tension (MT) of the polyethylene resin compositions of the Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] I. Polyethylene resin composition The polyethylene resin composition of the present invention comprises, as an essential component, one or more ethylene polymers selected from the group consisting of ethylene homopolymers and copolymers of ethylene with an α-olefin having 3 to 12 carbon atoms, and is characterized by containing 15% by mass or more and 40% by mass or less of the following polyethylene component (A) and 60% by mass or more and 85% by mass or less of the following polyethylene component (B), and satisfying the following properties (1) to (6): Polyethylene component (A); Property (a1): The high melt flow rate (HLMFR) at a temperature of 190° C. and a load of 21.6 kg is 0.7 g / 10 min or more and 10.0 g / 10 min or less; Property (a2): Density is 0.915g / cm 3 More than 0.945g / cm 3 Polyethylene, which is: Polyethylene component (B); Property (b1): A melt flow rate (MFR) at a temperature of 190° C. and a load of 2.16 kg is 5.0 g / 10 min or more and 50.0 g / 10 min or less; Characteristics (b2): Density is 0.950g / cm 3More than 0.980g / cm 3 Polyethylene, which is: Property (1): The melt flow rate (MFR) measured at a temperature of 190°C and a load of 2.16 kg is greater than 1.0 g / 10 min and less than or equal to 5.0 g / 10 min. Property (2): The high melt flow rate (HLMFR) at a temperature of 190°C and a load of 21.6 kg is 30 g / 10 min or more and 300 g / 10 min or less. Property (3): The melt flow rate ratio (HLMFR / MFR), which is the ratio of HLMFR to MFR, is 10 or more and 60 or less. Characteristics (4): 0.940g / cm 3 More than 0.965g / cm 3 The following is the result. Property (5): The number average molecular weight (Mn) measured by gel permeation chromatography (GPC) is 8,600 or more, and the weight average molecular weight (Mw) is 91,000 or more. Property (6): The branching index, calculated by the following formula using the number of branches per 1,000 carbon atoms of each component at molecular weights of 50,000, 100,000, 200,000, 300,000 and 400,000 as measured by GPC-IR, is 2.34 or more. [Branch count index] = [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 50,000] x [X 5万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 100,000] × [X 10万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 200,000] × [X 20万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 300,000] × [X 30万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 400,000] × [X 40万 ] Where: [X 5万 ] = [weight fraction of molecular weight 50,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 10万] = [weight fraction of molecular weight 100,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 20万 ] = [weight fraction of molecular weight 200,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 30万 ] = [weight fraction of molecular weight 300,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 40万 ] = [weight fraction of molecular weight 400,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000 and 400,000] [Sum of weight fractions of molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000] = [(weight fraction of molecular weight of 50,000) + (weight fraction of molecular weight of 100,000) + (weight fraction of molecular weight of 200,000) + (weight fraction of molecular weight of 300,000) + (weight fraction of molecular weight of 400,000)]
[0019] The polyethylene resin composition of the present invention contains specific amounts of the specific polyethylene component (A) and the polyethylene component (B) and satisfies the properties (1) to (6), and thereby has the effect of providing a molded article or container that has good moldability in injection stretch blow molding, an excellent balance between rigidity, environmental stress crack resistance, and impact resistance of a molded article, high compatibility of resin components, and excellent appearance. The present invention will be described in detail below for each item. In the present invention, polyethylene refers generally to ethylene homopolymers and copolymers of ethylene with olefins described below, and may also be referred to as ethylene-based polymers. In addition, in this specification, the use of "to" indicating a numerical range is used to mean that the numerical values before and after it are included as the lower limit and upper limit.
[0020] 1. Constitution of polyethylene resin composition The polyethylene resin composition of the present invention contains, as essential components, one or more ethylene polymers selected from the group consisting of ethylene homopolymers and copolymers of ethylene with an α-olefin having 3 to 12 carbon atoms, and contains specific amounts of the polyethylene component (A) and the polyethylene component (B), and simultaneously satisfies the above properties (1) to (6). Moreover, the polyethylene resin composition of the present invention may further contain optional components described below in addition to the ethylene polymers, so long as the polyethylene resin composition simultaneously satisfies the above properties (1) to (6).
[0021] In the polyethylene resin composition of the present invention, the compositional proportions of the polyethylene component (A) and the polyethylene component (B) simultaneously satisfy the properties (1) to (6), and from the viewpoints of compatibility of the resin composition and appearance of a molded product, the polyethylene component (A) is contained in an amount of 15% by mass or more and 40% by mass or less, and the polyethylene component (B) is contained in an amount of 60% by mass or more and 85% by mass or less. In particular, the polyethylene resin composition of the present invention preferably contains the polyethylene component (A) in an amount of 20% by mass or more and 35% by mass or less, and the polyethylene component (B) in an amount of 65% by mass or more and 80% by mass or less, and more preferably contains the polyethylene component (A) in an amount of 25% by mass or more and 30% by mass or less, and the polyethylene component (B) in an amount of 70% by mass or more and 75% by mass or less.
[0022] 1-1.Polyethylene component (A) Characteristics (a1) The polyethylene component (A) used in the present invention is selected from those having an HLMFR of 0.7 g / 10 min or more and 10 g / 10 min or less from the viewpoints of fluidity and long-term durability. The lower limit of the HLMFR of the polyethylene component (A) is preferably 1.0 g / 10 min or more, more preferably 1.4 g / 10 min or more, and the upper limit of the HLMFR is preferably 5.0 g / 10 min or less, more preferably 3.0 g / 10 min or less. If the HLMFR is less than the lower limit, the MFR of the final resin composition will not be within the specified range, and the flowability will decrease, which may lead to poor moldability in injection stretch blow molding, and poor compatibility, which may impair the appearance of the molded article. On the other hand, if the HLMFR exceeds the upper limit, the environmental stress crack resistance of the final resin composition will not be achieved, and the long-term durability of the molded article may decrease. The HLMFR can be adjusted mainly by the amount of hydrogen and the polymerization temperature during polymerization of the polyethylene component (A).
[0023] Characteristics (a2) The polyethylene component (A) used in the present invention has a density of 0.915 g / cm3 from the viewpoints of impact resistance and environmental stress crack resistance. 3 More than 0.945g / cm 3 The lower limit of the density of the polyethylene component (A) is preferably 0.919 g / cm 3 The upper limit of the density is preferably 0.930 g / cm 3 Less than or equal to 0.925 g / cm 3 More preferably, 0.920 g / cm 3 The following is the result. If the density is less than the lower limit, the density range of the final resin composition cannot be achieved, and the rigidity may be insufficient, whereas if the density is more than the upper limit, the impact resistance and environmental stress crack resistance of the final resin composition may be reduced. The density can be adjusted mainly by the amount of α-olefin during polymerization of the polyethylene component (A).
[0024] Characteristics (a3) It is preferable that the polyethylene component (A) used in the present invention further satisfies the following property (a3) in terms of compatibility, appearance of the molded product, and the like. Property (a3): The molecular weight distribution, which is expressed as the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured by gel permeation chromatography (GPC), is 2.0 or more and 10.0 or less. The molecular weight distribution (Mw / Mn) of the polyethylene component (A) preferably has a lower limit of 2.5 or more, more preferably 3.0 or more, and an upper limit of 6.0 or less, more preferably 5.0 or less. When the molecular weight distribution (Mw / Mn) of the polyethylene component (A) used in the present invention is equal to or higher than the lower limit, the compatibility of each ethylene polymer component constituting the polyethylene resin composition becomes better, and the deterioration of the physical properties such as the impact resistance and environmental stress crack resistance of the polyethylene resin composition of the present invention is easily suppressed, and the appearance of the molded article becomes good, which is preferable. In addition, the flowability of the polyethylene resin composition of the present invention becomes good, and therefore, the moldability in injection stretch blow molding becomes good, which is preferable. On the other hand, when the molecular weight distribution (Mw / Mn) of the polyethylene component (A) is equal to or lower than the upper limit, the long-term durability and impact resistance of the final resin composition are easily improved.
[0025] The polyethylene component (A) used in the present invention may be produced by any production method as long as it satisfies the above-mentioned specific characteristics, but it can be preferably produced by polymerization using a specific metallocene catalyst as a polymerization catalyst. Among the metallocene catalysts, catalysts having a metallocene complex of a specific structure are preferred, and in particular, metallocene complexes having a cyclopentadienyl ring and a heterocyclic aromatic group, or metallocene complexes having a cyclopentadienyl ring and a fluorenyl ring are preferred.
[0026] The polyethylene component (A) is preferably polymerized by a metallocene catalyst containing Ti, Zr or Hf. Examples of the metallocene catalyst include a combination of a complex called a metallocene complex, in which a ligand having a cyclopentadiene skeleton is coordinated to a transition metal, and a co-catalyst. Specific examples of the metallocene catalyst include a combination of a metallocene complex in which a ligand having a cyclopentadiene skeleton such as methylcyclopentadiene, dimethylcyclopentadiene, or indene is coordinated to a transition metal such as Ti, Zr, or Hf, and an organometallic compound of an element in Groups 1 to 3 of the periodic table, such as aluminoxane, as a co-catalyst, and a supported type in which these complex catalysts are supported on a carrier such as silica.
[0027] The metallocene catalyst used in the present invention contains the following catalyst component (i) and catalyst component (ii), and is a catalyst obtained by combining with catalyst component (iii) as necessary. Catalyst component (i): metallocene complex Catalyst component (ii): a compound that reacts with catalyst component (i) to form a cationic metallocene compound. Catalyst component (iii): fine particle support
[0028] (1) Catalyst component (i) The catalyst component (i) is a metallocene compound of a transition metal of Group 4 of the periodic table, specifically, a compound represented by the following general formulas (I) to (VII).
[0029] (C5H 5-a R 1 a )(C5H 5-b R 2 b )MXY General formula (I) Q 1 (C5H 4-c R 1 c )(C5H 4-d R 2 d )MXY General formula (II) Q 2 (C5H 4-e R3 e )ZMXY General formula (III) (C5H 5-f R 3 f )ZMXY General formula (IV) (C5H 5-f R 3 f )MXYW General formula (V) Q 3 (C5H 5-g R 4 g )(C5H 5-h R 5 h )MXY General formula (VI) Q 4 Q 5 (C5H 3-i R 6 i )(C5H 3-j R 7 j )MXY General formula (VII)
[0030] Here, Q 1 , Q 4 , Q 5 represents a linking group that bridges two conjugated five-membered ring ligands, and Q 2 represents a linking group that bridges the conjugated five-membered ring ligand and the Z group, and Q represents a linking group that bridges the conjugated five-membered ring ligand and the Z group. 3 is R 4 and R 5 M is a transition metal of Group 3 to 12 of the periodic table, X, Y and W each independently represent hydrogen, halogen, a hydrocarbon group having 1 to 20 carbon atoms, an oxygen-containing hydrocarbon group having 1 to 20 carbon atoms, a nitrogen-containing hydrocarbon group having 1 to 20 carbon atoms, a phosphorus-containing hydrocarbon group having 1 to 20 carbon atoms or a silicon-containing hydrocarbon group having 1 to 20 carbon atoms, Z is a ligand containing oxygen or sulfur, a silicon-containing hydrocarbon group having 1 to 40 carbon atoms, a nitrogen-containing hydrocarbon group having 1 to 40 carbon atoms or a phosphorus-containing hydrocarbon group having 1 to 40 carbon atoms. M is preferably a transition metal of Group 4 such as Ti, Zr or Hf.
[0031] R 1 ~R 7each independently represents a hydrocarbon group having 1 to 20 carbon atoms, a halogen group, a halogen-containing hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group, an aryloxy group, an oxygen-containing hydrocarbon group, a silicon-containing hydrocarbon group, a phosphorus-containing hydrocarbon group, a nitrogen-containing hydrocarbon group, or a boron-containing hydrocarbon group. 1 ~R 5 It is preferable that at least one of the heterocyclic aromatic groups is a heterocyclic aromatic group. Among the heterocyclic aromatic groups, a furyl group, a benzofuryl group, a thienyl group, and a benzothienyl group are preferable, and a furyl group and a benzofuryl group are more preferable. These heterocyclic aromatic groups may have a hydrocarbon group having 1 to 20 carbon atoms, a halogen group, a halogen-containing hydrocarbon group having 1 to 20 carbon atoms, an oxygen-containing hydrocarbon group, a silicon-containing hydrocarbon group, a phosphorus-containing hydrocarbon group, a nitrogen-containing hydrocarbon group, or a boron-containing hydrocarbon group, and in this case, a hydrocarbon group having 1 to 20 carbon atoms and a silicon-containing hydrocarbon group are preferable. In addition, when two adjacent R 1 , 2 R 2 , 2 R 3 , 2 R 4 , 2 R 5 , 2 R 6 , or two R 7 may be bonded to each other to form a ring having 4 to 10 carbon atoms. a, b, c, d, e, f, g, h, i and j are integers which satisfy 0≦a≦5, 0≦b≦5, 0≦c≦4, 0≦d≦4, 0≦e≦4, 0≦f≦5, 0≦g≦5, 0≦h≦5, 0≦i≦3, 0≦j≦3.
[0032] A linking group Q bridging two conjugated five-membered ring ligands 1 , Q 4 , Q 5 , a bonding group Q bridging the conjugated five-membered ring ligand and the Z group 2 , and R 4 and R 5 Q 3Specific examples of the silyl group include the following: alkylene groups such as methylene and ethylene groups, alkylidene groups such as ethylidene, propylidene, isopropylidene, phenylmethylidene and diphenylmethylidene groups, silicon-containing crosslinking groups such as dimethylsilylene, diethylsilylene, dipropylsilylene, diphenylsilylene, methylethylsilylene, methylphenylsilylene, methyl-t-butylsilylene, disilylene and tetramethyldisilylene groups, germanium-containing crosslinking groups, alkylphosphines, amines, etc. Among these, alkylene groups, alkylidene groups, silicon-containing crosslinking groups and germanium-containing crosslinking groups are particularly preferably used.
[0033] Specific examples of Zr complexes represented by the above general formulas (I), (II), (III), (IV), (V), (VI) and (VII) include the compounds described in paragraphs 0045 to 0055 of JP 2017-179304 A, and compounds in which Zr in the specific examples is replaced with Hf or Ti can also be used. In addition, the metallocene complexes represented by the general formulas (I), (II), (III), (IV), (V), (VI) and (VII) can be used as a mixture of two or more compounds represented by the same general formula or different general formulas.
[0034] Among the catalyst components (i) described above, the preferred metallocene complex for producing the polyethylene component (A) is preferably a metallocene complex represented by general formula (I) or general formula (II), and among them, a metallocene complex having a cyclopentadienyl ring and a heterocyclic aromatic group is preferred, and further, a metallocene complex having an indenyl ring skeleton is preferred. From the viewpoint of being able to produce a high molecular weight polymer and being excellent in copolymerization in copolymerization of ethylene with other α-olefins, a metallocene complex represented by general formula (II) is preferred, and a metallocene complex represented by general formula (II) having an indenyl ring skeleton is most preferred. Being able to produce a high molecular weight substance has the advantage that polymers of various molecular weights can be designed by a method of adjusting the molecular weight of various polymers as described below. Furthermore, from the viewpoint of being able to produce polyethylene having a high molecular weight and long chain branches, the following compound group is preferable among the metallocene complexes represented by the general formula (II).
[0035] In one preferred embodiment, the compound group is R 1 ~R 2 The bridged metallocene complex contains at least one heterocyclic aromatic group in the compound as a heterocyclic aromatic group. Preferred heterocyclic aromatic groups include a group consisting of a furyl group, a benzofuryl group, a thienyl group, and a benzothienyl group. These substituents may further have a substituent such as a silicon-containing group. Among the substituents selected from the group consisting of a furyl group, a benzofuryl group, a thienyl group, and a benzothienyl group, a furyl group and a benzofuryl group are more preferred. Furthermore, it is preferred that these substituents are introduced at the 2-position of a substituted cyclopentadienyl group or a substituted indenyl group, and it is particularly preferred that the compound has at least one substituted cyclopentadienyl group that does not have another condensed ring structure.
[0036] By using these compounds as metallocene complexes and further by adopting specific polymerization conditions, the polyethylene component (A) preferred in the present invention can be easily produced.
[0037] These metallocene complexes are preferably used as supported catalysts as described below. In the first compound group, it is believed that the interaction between the so-called heteroatoms contained in the furyl group or thienyl group and the solid acid on the support causes non-uniformity in the active site structure, making it easier to generate long chain branches. In the second compound group, it is believed that the space around the active site changes by making it a supported catalyst, making it easier to generate long chain branches.
[0038] (2) Catalyst component (ii) The process for producing the polyethylene component (A) according to the present invention preferably contains, as essential components of the olefin polymerization catalyst, in addition to the above-mentioned catalyst component (i), a compound (catalyst component (ii)) that reacts with the metallocene compound of the catalyst component (i) to form a cationic metallocene compound, and, as necessary, a fine particle carrier (catalyst component (iii)).
[0039] One example of the catalyst component (ii) is an organoaluminum oxy compound. The organoaluminum oxy-compound has an Al-O-Al bond in the molecule, and the number of bonds is usually in the range of 1 to 100, preferably 1 to 50. Such an organoaluminum oxy-compound is usually a product obtained by reacting an organoaluminum compound with water. The reaction of organoaluminum with water is usually carried out in an inert hydrocarbon (solvent). Examples of the inert hydrocarbon that can be used include aliphatic hydrocarbons, alicyclic hydrocarbons, and aromatic hydrocarbons such as pentane, hexane, heptane, cyclohexane, methylcyclohexane, benzene, toluene, and xylene, but it is preferable to use an aliphatic hydrocarbon or an aromatic hydrocarbon.
[0040] As the organoaluminum compound used in the preparation of the organoaluminum oxy-compound, any compound represented by the following general formula (VIII) can be used, but it is preferable to use a trialkylaluminum. R a t AIX a 3-t General formula (VIII) (In general formula (VIII), R a represents a hydrocarbon group having 1 to 18 carbon atoms, preferably 1 to 12 carbon atoms, such as an alkyl group, an alkenyl group, an aryl group, or an aralkyl group; X a represents a hydrogen atom or a halogen atom, and t represents an integer of 1≦t≦3.
[0041] The alkyl group of the trialkylaluminum may be any of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, hexyl, octyl, decyl, and dodecyl groups, with the methyl group being particularly preferred. The above organoaluminum compounds can also be used in combination of two or more.
[0042] The reaction ratio of water to the organoaluminum compound (water / Al molar ratio) is preferably 0.25 / 1 to 1.2 / 1, particularly preferably 0.5 / 1 to 1 / 1, and the reaction temperature is usually in the range of -70 to 100°C, preferably -20 to 20°C. The reaction time is usually selected in the range of 5 minutes to 24 hours, preferably 10 minutes to 5 hours. As the water required for the reaction, not only simple water but also water of crystallization contained in copper sulfate hydrate, aluminum sulfate hydrate, etc., and components that can generate water in the reaction system can be used. Among the above-mentioned organoaluminum oxy compounds, those obtained by reacting alkylaluminum with water are usually called aluminoxanes, and in particular, methylaluminoxane (including those essentially consisting of methylaluminoxane (MAO)) is a suitable organoaluminum oxy compound. Of course, two or more of the above-mentioned organoaluminum oxy compounds may be used in combination as the organoaluminum oxy compound, and the organoaluminum oxy compound may be used in the form of a solution or dispersion in the above-mentioned inert hydrocarbon solvent.
[0043] Other specific examples of the catalyst component (ii) include borane compounds and borate compounds. Specific examples of the borane compounds and borate compounds include the compounds described in paragraphs 0065 to 0077 of JP2017-179304A.
[0044] A more particularly preferred catalyst component (ii) is an organoaluminum oxy compound. By using these compounds as the catalyst component (ii) and further by adopting specific polymerization conditions, the polyethylene component (A) preferred in the present invention can be easily produced.
[0045] (3) Catalyst component (iii) The particulate support which is the catalyst component (iii) may be an inorganic support, a particulate polymer support, or a mixture thereof. The inorganic support may be a metal, a metal oxide, a metal chloride, a metal carbonate, a carbonaceous material, or a mixture thereof. Suitable metals that can be used in the inorganic support include, for example, iron, aluminum, nickel, and the like.
[0046] Furthermore, examples of metal oxides include single oxides or composite oxides of elements in Groups 1 to 14 of the periodic table. Examples of such metal oxides include various natural or synthetic single oxides or composite oxides such as SiO2, Al2O3, MgO, CaO, B2O3, TiO2, ZrO2, Fe2O3, Al2O3·MgO, Al2O3·CaO, Al2O3·SiO2, Al2O3·MgO·CaO, Al2O3·MgO·SiO2, Al2O3·CuO, Al2O3·Fe2O3, Al2O3·NiO, and SiO2·MgO. Here, the above formula is not a molecular formula but represents only the composition, and the structure and catalyst component ratio of the composite oxide used in the present invention are not particularly limited. Furthermore, the metal oxide used in the present invention may absorb a small amount of moisture and may contain a small amount of impurities.
[0047] As the metal chloride, for example, chlorides of alkali metals and alkaline earth metals are preferable, and specifically, MgCl2, CaCl2, etc. are particularly suitable. As the metal carbonate, alkali metal or alkaline earth metal carbonate is preferable, and specific examples thereof include magnesium carbonate, calcium carbonate, barium carbonate, and the like. Examples of the carbonaceous material include carbon black and activated carbon. Any of the above inorganic carriers can be suitably used in the present invention, with metal oxides, silica, alumina and the like being particularly preferred.
[0048] These inorganic supports are preferably used after being calcined usually at 200 to 800° C., preferably 400 to 600° C., in air or in an inert gas such as nitrogen or argon, and the amount of surface hydroxyl groups is adjusted to 0.8 to 1.5 mmol / g. The properties of these inorganic carriers are not particularly limited, but usually, the average particle size is 5 to 200 μm, preferably 10 to 150 μm, the average pore size is 20 to 1000 Å, preferably 50 to 500 Å, and the specific surface area is 150 to 1000 m. 2 / g, preferably 200 to 700m 2 / g, pore volume is 0.3-2.5 cm 3 / g, preferably 0.5 to 2.0 cm 3 / g, apparent specific gravity is 0.10~0.50g / cm 3 It is preferable to use an inorganic carrier having the following formula:
[0049] The above-mentioned inorganic supports can be used as they are, of course, but can also be used after being contacted with an organoaluminum compound such as trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, tripropylaluminum, tributylaluminum, trioctylaluminum, tridecylaluminum or diisobutylaluminum hydride or an organoaluminum oxy compound containing an Al-O-Al bond as a pretreatment.
[0050] Further particularly preferred examples of the catalyst component (iii) include SiO2, Al2O3, and Al2O3·SiO2. By using these compounds as the catalyst component (iii) and further by adopting specific polymerization conditions, the polyethylene component (A) preferred in the present invention can be easily produced.
[0051] (4) Contact method, etc. In the metallocene catalyst according to the present invention, the method for contacting each component when obtaining a catalyst comprising the catalyst component (i), the catalyst component (ii), and, if necessary, the catalyst component (iii) is not particularly limited, and for example, the following methods can be arbitrarily adopted.
[0052] Contact method (1): The catalyst component (i) is contacted with the catalyst component (ii), and then the catalyst component (iii) is contacted. Contact method (2): The catalyst component (i) is contacted with the catalyst component (iii), and then the catalyst component (ii) is contacted. Contact method (3): catalytic component (ii) is contacted with catalytic component (iii), and then catalytic component (i) is contacted therewith.
[0053] Among these contact methods, contact methods (1) and (3) are preferred, and contact method (1) is the most preferred. In any of the contact methods, a method is adopted in which the components are contacted with or without stirring in an inert atmosphere such as nitrogen or argon, generally in the presence of a liquid inert hydrocarbon, such as an aromatic hydrocarbon (usually having 6 to 12 carbon atoms) such as benzene, toluene, xylene, ethylbenzene, etc., or an aliphatic or alicyclic hydrocarbon (usually having 5 to 12 carbon atoms) such as heptane, hexane, decane, dodecane, cyclohexane, etc. This contact is desirably carried out usually at a temperature of -100°C to 200°C, preferably -50°C to 100°C, and more preferably 0°C to 50°C, for 5 minutes to 50 hours, preferably 30 minutes to 24 hours, and more preferably 30 minutes to 12 hours.
[0054] In addition, when the catalyst component (i), the catalyst component (ii) and the catalyst component (iii) are contacted with each other, as described above, either an aromatic hydrocarbon solvent in which a certain component is soluble or slightly soluble, or an aliphatic or alicyclic hydrocarbon solvent in which a certain component is insoluble or slightly soluble can be used.
[0055] When the contact reaction between each component is carried out stepwise, the solvent used in the previous step may be used as it is as the solvent for the contact reaction in the subsequent step without removing it. After the contact reaction in the previous step using a soluble solvent, a liquid inert hydrocarbon in which some components are insoluble or poorly soluble (e.g., aliphatic hydrocarbons, alicyclic hydrocarbons, or aromatic hydrocarbons such as pentane, hexane, decane, dodecane, cyclohexane, benzene, toluene, and xylene) is added to recover the desired product as a solid, or after removing a part or all of the soluble solvent by drying or other means to recover the desired product as a solid, the contact reaction in the subsequent step of the desired product may be carried out using any of the above-mentioned inert hydrocarbon solvents. In the present invention, the contact reaction of each component may be carried out multiple times.
[0056] In the present invention, the ratio of the catalyst components (i), (ii) and (iii) used is not particularly limited, but the following range is preferred.
[0057] When an organoaluminum oxy compound is used as the catalyst component (ii), the atomic ratio (Al / M) of aluminum in the organoaluminum oxy compound to the transition metal (M) in the catalyst component (i) is usually in the range of 1 to 100,000, preferably 5 to 1,000, and more preferably 50 to 200. When a borane compound or a borate compound is used, the atomic ratio (B / M) of boron to the transition metal (M) in the metallocene compound is usually in the range of 0.01 to 100, preferably 0.1 to 50, and more preferably 0.2 to 10. Furthermore, when a mixture of an organoaluminum oxy compound, a borane compound and a borate compound is used as the catalyst component (ii), it is desirable to select the use ratio of each compound in the mixture relative to the transition metal (M) in the same manner as above.
[0058] The amount of catalyst component (iii) used is 1 g per 0.0001 to 5 mmol, preferably per 0.001 to 0.5 mmol, and more preferably per 0.01 to 0.1 mmol of the transition metal in catalyst component (i).
[0059] The catalyst for olefin polymerization can be obtained as a solid catalyst by contacting the catalyst components (i), (ii) and (iii) with each other by any of the contact methods (1) to (3) and then removing the solvent. The solvent is desirably removed at normal pressure or reduced pressure, at 0 to 200°C, preferably 20 to 150°C, for 1 minute to 50 hours, preferably 10 minutes to 10 hours.
[0060] The metallocene catalyst can also be obtained by the following method. Contact method (4): The catalyst component (i) is contacted with the catalyst component (iii) to remove the solvent, thereby obtaining a solid catalyst component, which is then contacted with an organoaluminum oxy compound, a borane compound, a borate compound or a mixture thereof under polymerization conditions. Contact method (5): An organoaluminum oxy compound, a borane compound, a borate compound or a mixture thereof is contacted with catalyst component (iii) to remove the solvent, thereby obtaining a solid catalyst component, which is then contacted with catalyst component (i) under polymerization conditions. In the above contact methods (4) and (5), the component ratios, contact conditions and solvent removal conditions can be the same as those described above.
[0061] Furthermore, a layered silicate can also be used as a component serving as both the catalyst component (ii) and the catalyst component (iii), which are essential components in the process for producing the polyethylene component (A) according to the present invention. A layered silicate is a silicate compound that has a crystal structure in which planes formed by ionic bonds or the like are stacked in parallel with each other with weak bonding forces. Most layered silicates occur naturally as the main component of clay minerals, but these layered silicates are not limited to those that are naturally occurring, and may also be synthetically produced.
[0062] Among these, smectites, vermiculites, and micas, such as montmorillonite, sauconite, beidellite, nontronite, saponite, hectorite, stevensite, bentonite, and taeniolite, are preferred.
[0063] Generally, natural products are often non-ion-exchangeable (non-swellable), and in such cases, it is preferable to carry out a treatment to impart ion-exchangeability (or swelling property) to the product so that it has the desired ion-exchangeability (or swelling property). Among such treatments, the following chemical treatments are particularly preferable. The chemical treatment used here can be either a surface treatment for removing impurities adhering to the surface or a treatment that affects the crystal structure and chemical composition of the layered silicate. Specifically, examples of such treatments include (a) acid treatment using hydrochloric acid, sulfuric acid, etc., (b) alkali treatment using NaOH, KOH, NH3, etc., (c) salt treatment using salts consisting of a cation containing at least one atom selected from Groups 2 to 14 of the periodic table and at least one anion selected from the group consisting of halogen atoms or anions derived from inorganic acids, and (d) organic treatment using alcohols, hydrocarbon compounds, formamide, aniline, etc. These treatments may be performed alone or in combination of two or more.
[0064] The particle properties of the layered silicate can be controlled by pulverization, granulation, sizing, classification, etc. at any time before, during, or after all steps. The method can be any suitable method. In particular, examples of the granulation method include spray granulation, rolling granulation, compression granulation, stirring granulation, briquetting, compacting, extrusion granulation, fluidized bed granulation, emulsion granulation, and submerged granulation. Particularly preferred granulation methods are spray granulation, rolling granulation, and compression granulation.
[0065] The layered silicates described above can of course be used as they are, but these layered silicates can also be used in combination with an organoaluminum compound such as trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, trihexylaluminum, trioctylaluminum, tridecylaluminum, or diisobutylaluminum hydride, or an organoaluminum oxy compound containing an Al-O-Al bond.
[0066] In the metallocene catalyst according to the present invention, in order to support the catalyst component (i) on the layered silicate, the catalyst component (i) and the layered silicate may be brought into contact with each other, or the catalyst component (i), the organoaluminum compound, and the layered silicate may be brought into contact with each other. The method for contacting each component is not particularly limited, and for example, the following methods can be arbitrarily adopted. Contact method (6): The catalyst component (i) is contacted with an organoaluminum compound, and then contacted with a layered silicate support. Contact method (7): The catalyst component (i) is contacted with a layered silicate support, and then contacted with an organoaluminum compound. Contact method (8): The organoaluminum compound is contacted with the layered silicate support, and then contacted with the catalyst component (i).
[0067] Of these contact methods, contact methods (6) and (8) are preferred. In any of these contact methods, a method is employed in which the components are contacted with or without stirring in an inert atmosphere, usually nitrogen or argon, in the presence of a liquid inert hydrocarbon, such as aromatic hydrocarbons (usually having 6 to 12 carbon atoms) such as benzene, toluene, xylene, ethylbenzene, etc., and aliphatic or alicyclic hydrocarbons (usually having 5 to 12 carbon atoms) such as heptane, hexane, decane, dodecane, cyclohexane, etc.
[0068] The proportions of the catalyst component (i), the organoaluminum compound and the layered silicate support are not particularly limited, but the following ranges are preferred. The amount of the catalyst component (i) supported is 0.0001 to 5 mmol, preferably 0.001 to 0.5 mmol, and more preferably 0.01 to 0.1 mmol, per gram of the layered silicate support. When an organoaluminum compound is used, the amount of Al supported is desirably in the range of 0.01 to 100 mol, preferably 0.1 to 50 mol, and more preferably 0.2 to 10 mol.
[0069] The conditions for supporting and removing the solvent can be the same as those for the inorganic carrier described above. When a layered silicate is used as a component serving as both the catalyst component (ii) and the catalyst component (iii), the polymerization activity is high, and the productivity of the ethylene polymer having long chain branches is improved. The olefin polymerization catalyst thus obtained may be used after carrying out prepolymerization of monomers, if necessary.
[0070] As an example of the production of a metallocene catalyst, the catalyst can be produced by taking into consideration the "catalyst" and "raw material blend ratio and conditions" described in, for example, JP-T-2002-535339 and JP-A-2004-189869. The index of the polymer can be controlled by various polymerization conditions, for example, by the method described in JP-A-2-269705 and JP-A-3-21607.
[0071] The polyethylene component (A) is obtained by homopolymerization of ethylene or copolymerization of ethylene with an α-olefin having 3 to 12 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. Copolymerization with a diene is also possible for the purpose of modification. Examples of the diene compound used at this time include butadiene, 1,4-hexadiene, ethylidene norbornene, dicyclopentadiene, etc. The comonomer content during polymerization can be selected arbitrarily, but for example, in the case of copolymerization of ethylene with an α-olefin having 3 to 12 carbon atoms, the α-olefin content in the ethylene-α-olefin copolymer is 0.001 to 40 mol%, preferably 0.001 to 30 mol%, more preferably 0.001 to 5 mol%, even more preferably 0.001 to 2 mol%, and even more preferably 0.02 to 1.5 mol%. The ethylene used in each polyethylene component of the present invention may be ethylene produced from crude oil derived from normal fossil raw materials, or may be plant-derived ethylene. Examples of plant-derived ethylene and polyethylene include ethylene and its polymers described in JP-A-2010-511634. Plant-derived ethylene and its polymers are carbon-neutral (do not use fossil raw materials and do not lead to an increase in carbon dioxide in the atmosphere), making it possible to provide environmentally friendly products.
[0072] The molecular weight of the polymer produced can be adjusted to some extent by changing the polymerization conditions such as the polymerization temperature and the molar ratio of the catalyst, but the molecular weight can be adjusted more effectively by adding hydrogen to the polymerization reaction system. Furthermore, a component for removing water, a so-called scavenger, may be added to the polymerization system without any problem. Examples of such scavengers include organoaluminum compounds such as trimethylaluminum, triethylaluminum, and triisobutylaluminum, the organoaluminum oxy compounds, modified organoaluminum compounds containing branched alkyl groups, organozinc compounds such as diethylzinc and dibutylzinc, organomagnesium compounds such as diethylmagnesium, dibutylmagnesium, and ethylbutylmagnesium, and Grignard compounds such as ethylmagnesium chloride and butylmagnesium chloride. Among these, triethylaluminum, triisobutylaluminum, and ethylbutylmagnesium are preferred, and triethylaluminum is particularly preferred. The present invention can also be applied without any problems to a multi-stage polymerization method having two or more stages in which the polymerization conditions, such as hydrogen concentration, monomer amount, polymerization pressure, and polymerization temperature, are different from each other.
[0073] The polyethylene component (A) can be produced by a production process such as a gas phase polymerization method, a solution polymerization method, or a slurry polymerization method, and preferably the slurry polymerization method. The polymerization temperature among the polymerization conditions of the polyethylene component (A) can be selected from the range of 0 to 200°C. In the slurry polymerization, the polymerization is carried out at a temperature lower than the melting point of the produced polymer. The polymerization pressure can be selected from the range of atmospheric pressure to about 10 MPa. The polyethylene component (A) can be produced by carrying out slurry polymerization of ethylene and an α-olefin in the presence of an inert hydrocarbon solvent selected from aliphatic hydrocarbons such as hexane, heptane, and isobutane, aromatic hydrocarbons such as benzene, toluene, and xylene, and alicyclic hydrocarbons such as cyclohexane and methylcyclohexane, in a state substantially free of oxygen, water, and the like.
[0074] As long as the polyethylene component (A) satisfies the range specified in the present invention, it may be prepared by polymerization in a single polymerization vessel, or in a plurality of reactors connected in series or parallel in a continuous manner, or may be prepared by mixing a plurality of ethylene polymers which have been polymerized separately.
[0075] 1-2. Polyethylene component (B) Characteristics (b1) The polyethylene component (B) used in the present invention is selected from those having an MFR of 5.0 g / 10 min or more and 50.0 g / 10 min or less from the standpoint of fluidity and impact resistance. The lower limit of the MFR of the polyethylene component (B) is preferably 6.0 g / 10 min or more, more preferably 7.5 g / 10 min or more, and the upper limit of the MFR is preferably 30.0 g / 10 min or less, more preferably 20.0 g / 10 min or less. If the MFR is less than the lower limit, the molecular weight increases, and there is a risk that the flowability and moldability cannot be ensured. In addition, in the final resin composition, the HLMFR cannot be achieved within the specified range, and the flowability decreases, which may cause poor moldability and flow instability phenomena such as sharkskin and melt fracture to occur easily in injection stretch blow molding, thereby impairing the appearance of the molded product. On the other hand, if the MFR exceeds the upper limit, the amount of low molecular weight components increases, which may result in failure to ensure impact resistance. Also, the impact resistance of the final resin composition may not be achieved, and the drop impact resistance of the molded article may be reduced. The MFR can be adjusted mainly by the amount of hydrogen and the polymerization temperature during polymerization of the polyethylene component (B).
[0076] Characteristics (b2) The polyethylene component (B) used in the present invention has a density of 0.950 g / cm3 from the viewpoints of impact resistance and environmental stress crack resistance. 3 More than 0.980g / cm 3 The lower limit of the density of the polyethylene component (B) is preferably 0.960 g / cm 3 The upper limit of the density is preferably 0.970 g / cm 3 The following is the result. If the density of the polyethylene component (B) is less than the lower limit, the density range of the final resin composition cannot be achieved, and the rigidity may be insufficient. On the other hand, if the density exceeds the upper limit, the impact resistance and environmental stress crack resistance of the final resin composition may be reduced, and the drop impact resistance and long-term durability of the container may be poor. The density can be adjusted mainly by the amount of α-olefin during polymerization of the polyethylene component (B).
[0077] Characteristics (b3) It is preferable that the polyethylene component (B) further satisfies the following characteristic (b3) from the standpoints of compatibility and the appearance of the molded article. Property (b3): The molecular weight distribution, expressed as the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured by gel permeation chromatography (GPC), is 2.0 or more and 10.0 or less. The molecular weight distribution (Mw / Mn) of the polyethylene component (B) preferably has a lower limit of 3.0 or more, more preferably 5.0 or more, and an upper limit of 8.0 or less, more preferably 7.5 or less. When the molecular weight distribution (Mw / Mn) of the polyethylene component (B) used in the present invention is equal to or higher than the lower limit, the compatibility of each ethylene polymer component constituting the polyethylene resin composition becomes better, and the deterioration of the physical properties such as the impact resistance and environmental stress crack resistance of the polyethylene resin composition of the present invention is easily suppressed, and the appearance of the molded article becomes good, which is preferable. In addition, the flowability of the polyethylene resin composition of the present invention becomes good, and thus the moldability in injection stretch blow molding becomes good, which is preferable. On the other hand, when the molecular weight distribution (Mw / Mn) of the polyethylene component (B) is equal to or lower than the upper limit, the long-term durability and impact resistance of the final resin composition are easily improved.
[0078] The polyethylene component (B) used in the present invention is an ethylene homopolymer or an ethylene-α-olefin copolymer, and can be polymerized using various polymerization catalysts as long as the above-mentioned specifications are satisfied. The polyethylene component (B) used in the present invention can be produced by polymerization using a Ziegler-Natta catalyst or a metallocene catalyst, and is preferably an ethylene polymer derived from a Ziegler-Natta catalyst, and can be produced in accordance with the polymerization method of the polyethylene component (A). As the Ziegler-Natta catalyst, a conventionally known catalyst can be appropriately selected and used.
[0079] 2. Characteristics of polyethylene resin composition It is important that the polyethylene resin composition of the present invention satisfies the following properties (1) to (6). Characteristics (1) From the viewpoints of fluidity and long-term durability, the polyethylene resin composition of the present invention is selected to have a melt flow rate (MFR) of more than 1.0 g / 10 min and not more than 5.0 g / 10 min, measured at a temperature of 190° C. and a load of 2.16 kg. The lower limit of the MFR is preferably 1.1 g / 10 min or more, more preferably 1.2 g / 10 min or more, and particularly preferably 1.3 g / 10 min or more, and the upper limit of the MFR is preferably 4.0 g / 10 min or less, more preferably 3.0 g / 10 min or less, and particularly preferably 2.5 g / 10 min or less. If the MFR is 1.0 g / 10 min or less, the fluidity will decrease, which may result in poor moldability, such as puncture of the container during injection stretch blow molding, or the appearance of the molded product may be impaired due to the increased likelihood of flow instability phenomena such as sharkskin and melt fracture. On the other hand, if the MFR exceeds 5.0 g / 10 min, impact resistance and environmental stress crack resistance cannot be achieved, and the drop impact resistance and long-term durability of the molded article may decrease. In the present invention, the MFR can be measured in accordance with JIS K6922-2:1997. The MFR of the polyethylene resin composition can be adjusted by the amount of hydrogen of each ethylene polymer component constituting the polyethylene resin composition, the temperature, and the amount of each component.
[0080] Characteristics (2) From the viewpoints of fluidity and long-term durability, the polyethylene resin composition of the present invention is selected to have a melt flow rate (HLMFR) of 30 g / 10 min or more and 300 g / 10 min or less at a temperature of 190° C. and a load of 21.6 kg. The lower limit of the HLMFR is preferably 35 g / 10 min or more, more preferably 40 g / 10 min or more, and particularly preferably 45 g / 10 min or more, and the upper limit of the HLMFR is preferably 200 g / 10 min or less, more preferably 150 g / 10 min or less, and particularly preferably 130 g / 10 min or less. If the HLMFR is less than 30 g / 10 min, the flowability decreases, and there is a risk of the moldability being deteriorated, such as the container being punctured during injection stretch blow molding. On the other hand, if the HLMFR exceeds 300 g / 10 min, impact resistance and environmental stress crack resistance cannot be achieved, and the drop impact resistance and long-term durability of the molded article may decrease. In the present invention, the HLMFR can be measured in accordance with JIS K6922-2:1997. The HLMFR of the polyethylene resin composition can be adjusted by the amount of hydrogen and the temperature during polymerization of each of the ethylene polymer components constituting the polyethylene resin composition, as well as the blending amount of each component.
[0081] Characteristics (3) From the viewpoints of impact resistance and environmental stress crack resistance, the polyethylene resin composition of the present invention is selected to have a melt flow rate ratio (HLMFR / MFR), which is the ratio of HLMFR to MFR, of 10 or more and 60 or less. The lower limit of the melt flow rate ratio is preferably 20 or more, more preferably 30 or more. The upper limit of the melt flow rate ratio is preferably 55 or less, more preferably 45 or less. HLMFR / MFR is highly correlated with molecular weight distribution, and when HLMFR / MFR is large, the molecular weight distribution becomes broad, and when HLMFR / MFR is small, the molecular weight distribution becomes narrow. If HLMFR / MFR exceeds 60, there is a risk of the compatibility of each component deteriorating and impact resistance decreasing, and if HLMFR / MFR is less than 10, there is a risk of the melt tension decreasing, the tendency for flow instability such as sharkskin to occur, and the environmental stress cracking resistance decreasing. The HLMFR / MFR can be controlled mainly in accordance with the method for controlling the molecular weight distribution.
[0082] Characteristics (4) The polyethylene resin composition of the present invention has a density of 0.940 g / cm3 from the viewpoints of impact resistance and environmental stress crack resistance. 3 More than 0.965g / cm 3 The lower limit of the density is preferably 0.950 g / cm 3 More preferably, 0.951 g / cm 3 The upper limit of the density is preferably 0.960 g / cm 3 More preferably, 0.955 g / cm 3 The following is the result. Density 0.940g / cm 3 If the density is less than 0.965 g / cm3, the rigidity may be insufficient. 3 If it exceeds this limit, the impact resistance and environmental stress crack resistance may decrease. In the present invention, the density can be measured in accordance with JIS K6922-1,2:1997. The density can be adjusted by the amount of α-olefin during polymerization of each ethylene polymer component constituting the polyethylene resin composition, and can also be adjusted by the blending amount of each component.
[0083] Characteristics (5) The polyethylene resin composition of the present invention is selected from those having a number average molecular weight (Mn) of 8,600 or more and a weight average molecular weight (Mw) of 91,000 or more, as measured by gel permeation chromatography (GPC). The lower limit of Mn is preferably 10,200 or more, and more preferably 10,500 or more. The lower limit of the Mw is preferably 92,000 or more, and more preferably 93,000 or more. If Mn is less than 8,600 or Mw is less than 91,000, the impact strength may decrease. In the present invention, Mn and Mw can be measured by gel permeation chromatography (GPC). Mn and Mw can be adjusted by adjusting the temperature and hydrogen concentration during polymerization of each ethylene polymer component constituting the polyethylene resin composition, and Mn and Mw can be increased by lowering the polymerization temperature or the hydrogen concentration.
[0084] In the present invention, the molecular weight and molecular weight distribution can be measured by gel permeation chromatography (GPC) under the following conditions. [Measurement conditions] Equipment used: Polymer Char HT GPC-IR System Detector: IR-6 Measurement temperature: 145℃ Solvent: Orthodichlorobenzene (ODCB) (with trimethylphenol 3.6g / 18L added as an antioxidant) Column: Showa Denko Shodex HT-806M x 2 Flow rate: 1.0mL / min Injection volume: 20μL
[0085] [Sample preparation] Put 5-8 mg of sample into a vial and set it in the autosampler. Inject 8 mL of solvent (room temperature) with the autosampler and program it to dissolve at 150 °C for 2 hours. Use heptane as a flow marker for pump flow rate correction.
[0086] [Creating a calibration curve] A calibration curve is prepared using standard polystyrenes, and converted into polyethylene. The standard polystyrenes used are a sample set of Showdex Standard SM-105 manufactured by Showa Denko Co., Ltd., as well as n-eicosane and n-tetracontane.
[0087] [Molecular weight calculation] Measurements are performed under the above conditions, and chromatograms are recorded at sampling intervals of 1 s. From these chromatograms, differential molecular weight distribution curves and average molecular weight values (Mn, Mw, and Mz) are calculated using the method described in "Size Exclusion Chromatography" by Mori Sadao (Kyoritsu Shuppan), Chapter 4, pp. 51-60. However, in order to correct the molecular weight dependency of dn / dc, the height H from the baseline in the chromatogram is corrected. Chromatogram recording (data acquisition) and average molecular weight calculation are performed using dedicated software (GPC One, Polymer Char) on a PC with Microsoft OS Windows (registered trademark) XP installed.
[0088] Characteristics(6) The polyethylene resin composition of the present invention is selected from those having a branching index of 2.34 or more calculated by the following formula using the number of branches per 1,000 carbon atoms of each component at molecular weights of 50,000, 100,000, 200,000, 300,000 and 400,000 as measured by GPC-IR. The branching index is preferably 2.50 or more, more preferably 3.00 or more, and the upper limit is preferably 5.00 or less, preferably 4.95 or less, more preferably 4.90 or less. [Branch count index] = [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 50,000] x [X 5万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 100,000] × [X 10万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 200,000] × [X 20万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 300,000] × [X 30万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 400,000] × [X 40万 ] Where: [X 5万 ] = [weight fraction of molecular weight 50,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 10万 ] = [weight fraction of molecular weight 100,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 20万 ] = [weight fraction of molecular weight 200,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 30万 ] = [weight fraction of molecular weight 300,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 40万 ] = [weight fraction of molecular weight 400,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000 and 400,000] [Sum of weight fractions of molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000] = [(weight fraction of molecular weight of 50,000) + (weight fraction of molecular weight of 100,000) + (weight fraction of molecular weight of 200,000) + (weight fraction of molecular weight of 300,000) + (weight fraction of molecular weight of 400,000)] The number of branches per 1,000 carbon atoms of each component with molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000 is determined by measuring the concentrations of CH2 (methylene) and CH3 (methyl) by GPC-IR and obtaining a calibration curve of a standard sample with a known number of branches, and the number of carbon atoms in the branch is not particularly limited. As the standard sample with a known number of branches, five polyethylene samples with CH3 (methyl) of 2.6, 16.5, 21.0, 33.5, or 45.3 per 1,000 carbon atoms can be used. In addition, since the polyethylene component (A) and the polyethylene component (B) are contained in a predetermined amount, the number of carbon atoms in the branch is usually 4 to 10, and does not have so-called long chain branches, which can be said to be short chain branches. The branch number index calculated by the above formula can be said to be the sum of the products of the number of branches per 1,000 carbon atoms and the normalized weight fraction of each component at molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000, as measured by GPC-IR. When the "branch number index", which is the sum of the product of the number of branches per 1,000 carbon atoms and the normalized weight fraction of each component at molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000 as measured by GPC-IR, is 2.34 or more, impact strength tends to be high. It is presumed that by having a certain number or more of short chain branches in the high molecular weight component, the probability of the existence of tie molecules between crystals increases, resulting in high impact strength. If the branching index is less than 2.34, the impact strength and environmental stress crack resistance may decrease, whereas if the branching index is more than 5.00, the rigidity may decrease. The above requirements can be achieved by selecting the polymerization catalyst, polymerization conditions, and resin composition. Specifically, for example, by containing specific amounts of the polyethylene component (A) and the polyethylene component (B) as described above, it is possible to achieve a polyethylene resin composition having no long chain branching structure and having a specific or greater number of short chain branches.
[0089] The number of branches and weight fraction per 1,000 carbon atoms in the molecules of the polyethylene of the present invention having molecular weights of 50,000, 100,000, 200,000, 300,000 and 400,000 can be obtained from Polymer Char's IR-6, as with the molecular weight in property (5).
[0090] Characteristics (7) The polyethylene resin composition of the present invention further has a tensile impact strength (TIS) of 130 kJ / m 2 More preferably, it is 134 kJ / m or more. 2 More preferably, it is equal to or greater than this. In the present invention, the tensile impact strength (TIS) at 23°C (unit: kJ / m 2 ) can be measured by preparing a 1.5 mm compression molded sheet in accordance with JIS K6922-2, punching out a test piece with an S-shaped dumbbell in accordance with ASTM D1822, and measuring the elastic modulus at 23°C and 50% RH.
[0091] Characteristics(8) The polyethylene resin composition of the present invention has a tensile impact strength (TIS) (unit: kJ / m 2 It is preferable that the HLMFR (unit: g / 10 min) satisfies the relationship represented by the following formula (1). TIS≧1560×HLMFR -0.55 ·Formula (1) Generally, a polyethylene resin composition exhibiting high fluidity tends to have a low tensile impact strength, and therefore it is desirable for the polyethylene resin composition to have both high fluidity and good tensile impact strength. Formula (1) shows that the polyethylene resin composition of the present invention has a higher tensile impact strength corresponding to the HLMFR than conventional polyethylene resins. That is, in order to distinguish the polyethylene resin composition of the present invention from conventional ones, the tensile impact strength (TIS) is considered to be a function negatively correlated with an increase in HLMFR, and the parameters of the function are set, and the TIS of the polyethylene resin composition of the present invention is shown to be higher in relation to the HLMFR than the TIS defined by the function. Specifically, based on the data of the examples and comparative examples, the values of TIS and HLMFR that distinguish the examples from the comparative examples having a low TIS corresponding to the HLMFR are assumed, and the parameters of the relational equation that holds between the TIS and HLMFR are determined by the least squares method. Formula (1) can be satisfied by appropriately selecting specific components of the composition of the present invention. Specifically, it can be improved by increasing the amount of short chain branches introduced into the polyethylene component polymerized with a metallocene catalyst, which is responsible for the high molecular weight component of the polyethylene resin composition of the present invention, or by optimizing the molecular weight of the polyethylene component polymerized with a Ziegler-Natta catalyst, which is responsible for the low molecular weight component, and by adjusting these, formula (1) can be satisfied.
[0092] Characteristics (9) The polyethylene resin composition of the present invention preferably has a melt tension (MT) (unit: mN) measured at 190° C. and an HLMFR (unit: g / 10 min) that satisfy the relationship represented by the following formula (2). MT<876.94×HLMFR -0.844 ...Equation (2) Moreover, in the polyethylene resin composition of the present invention, it is more preferable that MT (unit: mN) and HLMFR (unit: g / 10 min) satisfy the relationship represented by the following formula (3). MT<543.99×HLMFR -0.849 ...Equation (3) Generally, a polyethylene resin composition exhibiting high fluidity tends to have a low melt tension, but it is desirable for the polyethylene resin composition to have both high fluidity and good melt tension. If the melt tension is too high, residual strain increases during injection molding of the preform, which may cause shrinkage of the preform during reheating, and defects such as punctures may occur during stretching. Formula (2) shows that the polyethylene resin composition of the present invention has a lower melt tension corresponding to the HLMFR than conventional polyethylene resins. That is, in order to distinguish the polyethylene resin composition of the present invention from the conventional ones, the melt tension (MT) is considered to be a function negatively correlated with an increase in HLMFR, the parameters of the function are set, and the MT of the polyethylene resin composition of the present invention is shown to be smaller in correspondence with the HLMFR than the MT defined by the function. Specifically, based on the data of the examples and comparative examples, the values of MT and HLMFR that distinguish the examples from the comparative examples having a high melt tension corresponding to the HLMFR are assumed, and the parameters of the relational equation that holds between the MT and HLMFR are determined by the least squares method. Formula (2) can be satisfied by appropriately selecting specific components of the composition of the present invention. Specifically, MT can be reduced by reducing the amount of long chain branching introduced into each polyethylene component constituting the polyethylene resin composition of the present invention, MT can be reduced by narrowing the molecular weight distribution of each polyethylene component, and MT can be reduced by increasing the blending amount of polyethylene component (B) described below, and formula (2) can be satisfied by adjusting these factors.
[0093] The polyethylene resin composition of the present invention preferably has a melt tension (MT) of 9 mN or more from the standpoint of moldability, and preferably has a melt tension (MT) of 20 mN or less from the standpoint of moldability into injection stretch blow containers. In the present invention, the melt tension of the polyethylene resin composition is determined by measuring the stress when the molten polyethylene resin composition is stretched at a constant speed, and can be measured under the following conditions. [Measurement conditions] Machine used: Toyo Seiki Co., Ltd., Capillograph 1B Nozzle diameter: 2.095mm Nozzle length: 8.0mm Inflow angle: 180°(flat) Extrusion speed: 15mm / min Take-off speed: 6.5m / min Measurement temperature: 190℃
[0094] Characteristics (10) The polyethylene resin composition of the present invention preferably has an FNCT (hours) of 100 hours or more, and more preferably 200 hours or more. In the present invention, the circumferential notch creep test can be performed in accordance with ISO DIS 16770. A test piece having a cross section of 4 mm x 4 mm is prepared by making a 1 mm notch with a razor blade all around the circumference of a square column measuring 6 mm x 6 mm x 11 mm, and a tensile stress equivalent to 3.7 MPa is applied to the specimen in pure water at 80°C. The time until the specimen breaks is measured and taken as the break time of the FNCT.
[0095] Characteristics(11) The polyethylene resin composition of the present invention further has a molecular weight distribution, expressed as the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn), measured by gel permeation chromatography (GPC), of preferably 11.5 or less, and more preferably 10.0 or less. The molecular weight distribution (Mw / Mn) measured by GPC is related to the improvement of various physical properties and flowability of a resin composition. The molecular weight distribution can be controlled within a desired range by using a catalyst capable of controlling the molecular weight distribution and suitable polymerization conditions, or, in the case of a bimodal or multimodal polymer, by adjusting the molecular weight of each component.
[0096] Characteristics (12) With regard to the polyethylene resin composition of the present invention, it is preferable that no inflection point in the extensional viscosity due to strain hardening is observed in a log-log plot of the extensional viscosity η(t) (unit: Pa sec) measured at a temperature of 170°C and an extensional strain rate of 0.1 (unit: 1 / sec) versus the extension time t (unit: seconds). When the polyethylene resin composition of the present invention has a structure with long chain branches, inflection points of extensional viscosity due to strain hardening can be easily observed in a log-log plot of extensional viscosity η(t) (unit: Pa sec) measured at a temperature of 170°C and an elongational strain rate of 0.1 (unit: 1 / sec) versus elongation time t (unit: seconds). The fact that an inflection point in the extensional viscosity is not observed means that the polyethylene resin composition of the present invention does not have a long chain branching structure, or does not have such a long chain branching structure that an inflection point in the extensional viscosity is observed. The polyethylene resin composition of the present invention is required to have a predetermined number of short chain branches or more, and preferably has no long chain branching structure, in order to achieve good moldability in injection stretch blow molding, an excellent balance between the rigidity of a molded article and the environmental stress crack resistance and impact resistance, high compatibility with resin components, and excellent appearance of a molded article. The absence of long chain branches results in less residual strain during injection preform molding, which in turn prevents the preform from shrinking when reheated and reduces the likelihood of defects such as punctures during stretching, resulting in a good distribution of the wall thickness of the molded container.
[0097] In this specification, the presence or absence of an inflection point in the extensional viscosity due to strain hardening can be observed in the measurement of the degree of strain hardening. Regarding the method of measuring the strain hardening degree, in principle, the same value can be obtained by any method as long as the uniaxial extensional viscosity can be measured. For example, the details of the measurement method and the measurement device are described in the publicly known document: Polymer 42 (2001) 8663. In measuring the polyethylene according to the present invention, preferred measuring methods and measuring instruments include the following.
[0098] Measurement method: Equipment: Rheometrics Ares Fixture: TA Instruments Extentional Viscosity Fixture ·Measurement temperature: 170℃ Strain rate: 0.1 / sec Preparation of test specimen: Press mold a sheet of 18mm x 10mm and 0.7mm thick.
[0099] Calculation method: The extensional viscosity at 170°C and a strain rate of 0.1 / s is plotted on a double logarithmic graph with time t (s) on the horizontal axis and extensional viscosity η(t) (Pa·s) on the vertical axis. On the double logarithmic graph, the maximum extensional viscosity until the strain amount reaches 4.0 after strain hardening is calculated as η Max (t1) (t1 is the time when the maximum elongational viscosity is shown), and the approximation line of the elongational viscosity before strain hardening is η Linear (t), then η Max (t1) / η Linear The value calculated as (t1) is defined as the degree of strain hardening (λmax). The presence or absence of strain hardening is determined by whether or not there is an inflection point where the extensional viscosity changes from an upwardly convex curve to a downwardly convex curve with the passage of time. Figures 1 and 2 are typical plots of extensional viscosity. Figure 1 shows a case where an inflection point of extensional viscosity is observed, and η Max (t1), η Linear (t1) is shown. Figure 2 shows the case where the inflection point of the extensional viscosity is not observed.
[0100] In order to prevent the polyethylene component from having a long chain branched structure, it is preferable to carry out the polymerization using a suitable polymerization catalyst, which is preferably selected from the polymerization catalysts mentioned above.
[0101] The polyethylene resin composition of the present invention is a polyethylene resin composition that contains 15% by mass or more and 40% by mass or less of the polyethylene component (A) and 60% by mass or more and 85% by mass or less of the polyethylene component (B) and simultaneously satisfies the properties (1) to (6). Therefore, it is possible to obtain a molded article that has excellent moldability in injection stretch blow molding, an excellent balance of rigidity, environmental stress crack resistance, and impact resistance, and excellent appearance. Furthermore, a polyethylene resin composition having preferably one or more of the above properties (7) to (12) in addition to the above properties (1) to (6) can further enhance the above effects.
[0102] The effects achieved by the polyethylene resin composition of the present invention will be further described below. Generally speaking, extrusion blow molding is the mainstream method for blow molding of polyethylene, but the application of injection stretch blow molding is being considered because it does not produce flash during molding and the container properties are improved by the stretching effect. However, ordinary polyethylene materials for extrusion blow molding have low fluidity to suppress drawdown, and tend to have high tension when melted, which causes the surface of the injection preform to become rough, causes the preform to shrink when reheated, and is prone to molding defects during stretch blow molding. On the other hand, polyethylene materials for fibers have sufficient fluidity and low melt tension, so there are no problems with molding, but they have a low molecular weight and tend to lack impact strength and stress cracking resistance for some applications such as detergent containers. Therefore, there is a demand for a polyethylene resin composition that has fluidity suitable for injection stretch blow molding and can also be used in applications with high physical requirements. In contrast, the present invention provides a polyethylene resin composition which contains a specific polyethylene component (A) and a specific polyethylene component (B) in specific amounts, which satisfies a specific MFR, a specific HLMFR, a specific HLMFR / MFR ratio, and a specific density, which has a specific or higher number average molecular weight (Mn) and weight average molecular weight (Mw), and which has a specific or higher branching index. This improves the balance of rigidity, environmental stress cracking resistance, impact resistance, and the like of a molded product in proportion to flowability, and achieves a polyethylene resin composition which has excellent moldability in injection stretch blow molding, high compatibility of the resin components, and excellent appearance of the molded product.
[0103] 3. Method for producing polyethylene resin composition The polyethylene resin composition of the present invention contains, as essential components, one or more ethylene polymers selected from the group consisting of ethylene homopolymers and copolymers of ethylene and an α-olefin having 3 to 12 carbon atoms, and contains 15% by mass or more and 40% by mass or less of the polyethylene component (A) and 60% by mass or more and 85% by mass or less of the polyethylene component (B), and is not particularly limited as long as it is possible to produce a polyethylene resin composition that satisfies the above properties (1) to (6). The polyethylene resin composition of the present invention is preferably produced by melt-mixing the polyethylene component (A) and the polyethylene component (B) in a predetermined blending ratio, and by adding and melt-mixing other components as necessary, in view of ease of producing a resin composition satisfying the above-mentioned properties (1) to (6), excellent compatibility between the resin components, and excellent appearance of a molded product.
[0104] In addition to the polyethylene component (A) and the polyethylene component (B), the polyethylene resin composition of the present invention may contain the following substances as optional components within the scope of the present invention. For example, various ethylene polymers and their modifications can be used, such as high density polyethylene, low density polyethylene, high pressure polyethylene, polar monomer graft modified polyethylene, ethylene wax, ultra-high molecular weight polyethylene, ethylene elastomer, etc. The addition of high density polyethylene is preferable for improving rigidity, heat resistance, impact strength, etc. The addition of low density polyethylene is preferable for improving flexibility, impact strength, easy adhesion, transparency, low temperature strength, etc. The addition of high-pressure polyethylene is preferable for improving flexibility, easy adhesion, transparency, low-temperature strength, moldability, etc. The addition of polar monomer graft-modified polyethylene such as maleic acid-modified polyethylene, ethylene-acrylic acid derivative copolymer, ethylene-vinyl acetate copolymer, etc. is preferable for improving flexibility, easy adhesion, colorability, affinity with various materials, gas barrier properties, etc. The addition of ethylene-based wax is preferable for improving colorability, affinity with various materials, moldability, etc. The addition of ultra-high molecular weight polyethylene is preferable for improving mechanical strength, abrasion resistance, etc. The addition of ethylene-based elastomer is preferable for improving flexibility, mechanical strength, impact strength, etc. When the polyethylene component (A) and the polyethylene component (B) satisfying the specific balance of physical properties are mixed in specific amounts and used, a resin that acts as a compatibilizer for the polyethylene component (A) which is a high molecular weight component and the polyethylene component (B) which is a low molecular weight component may be further added as a third component. In addition to the above polymers, various resins can be used, specifically, various nylon resins, various polyamides, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), various polyesters, polycarbonate resins, EVOH, EVA, PMMA, PMA, various engineering plastics, polylactic acid, celluloses, natural rubbers, polyurethane, PVC, fluorine-based resins such as Teflon (registered trademark), inorganic polymers such as silicone resins, etc.
[0105] The polyethylene resin composition of the present invention can be pelletized by mechanical melt mixing using a pelletizer, homogenizer or the like in a conventional manner, and then molded into a desired molded article using various molding machines. Furthermore, the polyethylene resin composition obtained by the above-mentioned method can be blended, in accordance with a conventional method, with other olefin-based polymers, rubbers and the like, as well as with known additives such as antioxidants, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, antifogging agents, antiblocking agents, processing aids, coloring pigments, crosslinking agents, foaming agents, inorganic or organic fillers, and flame retardants. As additives, for example, antioxidants (phenol-based, phosphorus-based, sulfur-based), lubricants, antistatic agents, light stabilizers, ultraviolet absorbers, etc. can be used in combination of one or more as appropriate. As fillers, calcium carbonate, talc, metal powders (aluminum, copper, iron, lead, etc.), silica stone, diatomaceous earth, alumina, gypsum, mica, clay, asbestos, graphite, carbon black, titanium oxide, etc. can be used, and among them, calcium carbonate, talc, mica, etc. are preferably used. In any case, various additives can be blended with the above-mentioned polyethylene resin composition as necessary, and the mixture can be kneaded with a kneading extruder, Banbury mixer, etc. to obtain a molding material.
[0106] In the present invention, a nucleating agent may be used to accelerate the crystallization rate of the polyethylene resin composition. The nucleating agent may be a commonly known one, and may be a general organic or inorganic nucleating agent, such as dibenzylidene sorbitol or a derivative thereof, an organic phosphoric acid compound or a metal salt thereof, an aromatic sulfonic acid salt or a metal salt thereof, an organic carboxylic acid or a metal salt thereof, a partial metal salt of rosin acid, inorganic fine particles such as talc, imides, amides, quinacridonequinones, or a mixture thereof. Among these, dibenzylidene sorbitol derivatives, organic metal phosphates, organic metal carboxylates, etc. are preferred because of their excellent transparency. Specific examples of dibenzylidene sorbitol derivatives include 1,3:2,4-bis(o-3,4-dimethylbenzylidene)sorbitol, 1,3:2,4-bis(o-2,4-dimethylbenzylidene)sorbitol, 1,3:2,4-bis(o-4-ethylbenzylidene)sorbitol, 1,3:2,4-bis(o-4-chlorobenzylidene)sorbitol, and 1,3:2,4-dibenzylidene sorbitol. Specific examples of metal benzoates include aluminum hydroxy-di(t-butylbenzoate).
[0107] When a nucleating agent is blended in the polyethylene resin composition of the present invention, the blending amount of the nucleating agent is preferably 0.01 to 5 parts by mass, more preferably 0.01 to 3 parts by mass, further preferably 0.01 to 1 part by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the composition. If the amount of the nucleating agent is less than 0.01 part by mass, the effect of improving high-speed moldability is insufficient, whereas if it exceeds 5 parts by mass, a problem occurs in that the nucleating agent is likely to aggregate and form lumps.
[0108] 4. Uses of polyethylene resin composition The polyethylene resin composition of the present invention has an excellent balance between the rigidity of the molded article, the environmental stress crack resistance, and the impact resistance, and also has excellent moldability, so that various molded articles can be produced by various molding methods. Since the polyethylene resin composition of the present invention has excellent flowability, it is preferably molded mainly by an injection stretch blow molding method or the like, and various molded articles such as hollow containers can be suitably obtained.
[0109] II. Molded body and container The molded article of the present invention can be produced by various molding methods using the polyethylene resin composition of the present invention as a raw material. The molded article of the present invention can be produced mainly by injection stretch blow molding, and various hollow molded articles such as hollow containers are suitable.
[0110] [Injection stretch blow molding method] Injection stretch blow molding is widely used to manufacture containers such as bottles using thermoplastic polymers. This process involves the production of a preform by injection molding and the expansion of this preform to the desired final shape. A distinction is generally made between one-stage (hot parison process) and two-stage (cold parison process). In the one-stage process, the production of the preform and the expansion of the preform to the desired final shape are carried out in the same production equipment. In the two-stage process, these two steps can be carried out in different production equipment and even in different locations; that is, the preform can be cooled to the molding environment temperature and transported to the location of the second production equipment, where it is reheated and expanded to the desired final shape. In general, the former one-stage process is also called the hot parison process and the latter two-stage process is also called the cold parison process.
[0111] The preform has an open end and a sealed end, and is manufactured by injection molding. The polyethylene resin composition of the present invention is fed to an extruder, plasticized, and injected under pressure into an injection mold through an opening called a gate. The polyethylene resin composition is then injected into the injection mold at an injection temperature of 180°C or higher, more preferably 185°C or higher, and most preferably 190°C or higher. The injection temperature of the polyethylene resin composition is 280°C or lower, preferably 275°C or lower, further preferably 270°C or lower, and suitably less than 210°C. The injection temperature is selected according to the MFR (or HLMFR) of the polyethylene resin composition. When the MFR (or HLMFR) is low, the injection temperature is increased, and when the MFR (or HLMFR) is high, the injection temperature is decreased. The preform is cooled inside the injection mold and then removed.
[0112] In the hot parison method, the preform is maintained at a temperature at least equal to or higher than the crystallization temperature, preferably equal to or higher than the melting point, specifically, the preform is maintained at a temperature of at least 125°C or higher, preferably equal to or higher than 140°C, more preferably equal to or higher than 141°C, and suitably equal to or higher than 145°C, and stretch blow molding is performed. These steps are preferably performed in a single manufacturing device. In the hot parison method, the molding process is generally known to be a four-step molding method in which the preform is injection molded, the temperature is adjusted, stretch blow molded, and the molded product is removed, and a three-step molding method in which the preform is injection molded, stretch blow molded, and the molded product is removed, and either molding method can be adopted in the present invention.
[0113] In the cold parison method, the preform can be cooled to the molding environment temperature and sent to another machine. The preform is reheated to a temperature at least equal to or higher than the crystallization temperature, preferably equal to or higher than the melting point, specifically, the preform is heated to a temperature of at least 125°C, preferably equal to or higher than 140°C, more preferably equal to or higher than 141°C, and suitably equal to or higher than 145°C. The preform is then transferred to a stretch blow molding process, where it is fixed inside a blow mold having the same shape as the final container shape, with the sealed end of the preform inside the blow mold.
[0114] In both the hot parison method and the cold parison method, in order to improve strength by forming oriented crystals during stretching, the polyethylene resin is generally biaxially stretched at a temperature lower than the melting point of the resin, for example, a temperature 10 to 20° C. lower than the melting point (JP Patent Publication 1984-140033). However, in the present invention, by using a specific polyethylene resin composition, stretch blow molding may be performed at a temperature higher than the crystallization temperature or melting point. In both the hot parison method and the cold parison method, if the stretching temperature is too low, the polyethylene resin composition is difficult to deform, a large force is required during stretching, and even if blow molding is performed, the expansion tends to be insufficient, whereas if the stretching temperature is too high, the polyethylene resin is not stretched during blow molding, and the improvement in strength due to the generation of oriented crystals tends not to be expected.
[0115] The preform is stretched axially by a central rod called the stretch rod, which moves the preform wall to the inner wall of the blow mold. Pressurized gas is blown in to radially stretch the preform to the shape of the blow mold. Blow molding can be carried out using gas at a pressure of 0.05-4 MPa, preferably 0.1-3 MPa. The blow molding of the preform can be carried out in two stages, i.e. first pre-blowing the preform at a low gas pressure and then blow molding the preform to its final shape at a higher gas pressure. The gas pressure in the pre-blow molding step (primary pressure) is in the range of 0.05-1 MPa, preferably in the range of 0.1-0.8 MPa. It is preferred that the gas pressure for blow molding the preform to its final shape (secondary pressure) is in the range of 0.5-4 MPa, preferably in the range of 0.5-3 MPa. Following stretch blow molding, the container is rapidly cooled and removed from the blow mold.
[0116] Since the polyethylene resin composition of the present invention satisfies the above-mentioned properties, it has good moldability without the occurrence of punctures, etc., in molding of injection stretch blow containers. The molded article of the present invention using the same has an excellent balance of rigidity, environmental stress cracking resistance and impact resistance, and is easy to have an excellent appearance. Since heat generation of the resin during the extrusion step is suppressed, the molding cycle can be shortened and the article can be produced with excellent production efficiency. Therefore, it is suitable for applications such as containers that require such properties, and can be suitably used for applications such as cosmetic containers, containers for detergents, shampoos and conditioners, or containers for foods such as edible oils. Since the polyethylene resin composition of the present invention satisfies the above-mentioned characteristics, it can be suitably used for the above-mentioned various containers with handles, particularly containers using the polyethylene resin composition of the present invention.
[0117] In particular, containers that are molded using the polyethylene resin composition of the present invention can be molded at high speed and with high cycle speed, and are excellent in product properties and economically advantageous, and are suitable as containers for detergents, shampoos, conditioners, etc. EXAMPLES
[0118] The present invention will be explained in more detail below by way of examples, but the present invention is not limited to these examples as long as it does not deviate from the gist of the invention.
[0119] 1.Measurement method The measurement methods used in the examples are as follows. (1)Melt flow rate (MFR) at 190°C and 2.16 kg load: Measurements were performed in accordance with JIS K6922-2:1997. (2) Melt flow rate (HLMFR) at 190°C and 21.6 kg load: Measurements were performed in accordance with JIS K6922-2:1997. (3) Density: Measurements were performed in accordance with JIS K6922-1,2:1997.
[0120] (4) Measurement of molecular weight, molecular weight distribution and branch number by gel permeation chromatography (GPC): The measurement was performed by gel permeation chromatography (GPC) under the following conditions. [Measurement conditions] Equipment used: Polymer Char HT GPC-IR System Detector: IR-6 Measurement temperature: 145℃ Solvent: Orthodichlorobenzene (ODCB) (with trimethylphenol 3.6g / 18L added as an antioxidant) Column: Showa Denko Shodex HT-806M x 2 Flow rate: 1.0mL / min Injection volume: 20μL
[0121] [Sample preparation] 5-8 mg of sample was placed in a vial and set in the autosampler. 8 mL of solvent (room temperature) was injected into the autosampler and programmed to dissolve at 150°C for 2 hours. Heptane was used as a flow marker for pump flow rate correction.
[0122] [Creating a calibration curve] A calibration curve was prepared using standard polystyrenes, and the values were converted to polyethylene. The standard polystyrenes used were the Showdex Standard SM-105 sample set, n-eicosane, and n-tetracontane.
[0123] [Molecular weight calculation] Measurement was performed under the above conditions, and the chromatogram was recorded at a sampling interval of 1 s. From this chromatogram, the differential molecular weight distribution curve and the average molecular weight values (Mn, Mw and Mz) were calculated by the method described in "Size Exclusion Chromatography" by Mori Sadao (Kyoritsu Shuppan), Chapter 4, pp. 51-60. From the differential molecular weight distribution curve, the weight fractions of molecular weights of 50,000, 100,000, 200,000, 300,000 and 400,000 were obtained. However, in order to correct the molecular weight dependency of dn / dc, the height H from the baseline in the chromatogram was corrected. The recording of the chromatogram (data acquisition) and the calculation of the average molecular weight were performed using dedicated software (GPC One, Polymer Char) on a PC installed with Microsoft's OS Windows (registered trademark) XP.
[0124] [Calculation of branch number index] The number of branches per 1,000 carbon atoms for each component with molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000 was determined by measuring the concentrations of CH2 (methylene) and CH3 (methyl) using GPC-IR and obtaining the number of branches per 1,000 carbon atoms from a calibration curve of standard samples with known branch numbers (five polyethylene samples with CH3 (methyl) per 1,000 carbon atoms of 2.6, 16.5, 21.0, 33.5, or 45.3). The branch number index was calculated from the branch number and weight fraction per 1,000 carbon atoms of each component at molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000, using the following formula. [Branch count index] = [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 50,000] x [X 5万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 100,000] × [X 10万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 200,000] × [X 20万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 300,000] × [X 30万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 400,000] × [X 40万 ] Where: [X 5万 ] = [weight fraction of molecular weight 50,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 10万 ] = [weight fraction of molecular weight 100,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 20万 ] = [weight fraction of molecular weight 200,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 30万 ] = [weight fraction of molecular weight 300,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 40万 ] = [weight fraction of molecular weight 400,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000 and 400,000] [Sum of weight fractions of molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000] = [(weight fraction of molecular weight of 50,000) + (weight fraction of molecular weight of 100,000) + (weight fraction of molecular weight of 200,000) + (weight fraction of molecular weight of 300,000) + (weight fraction of molecular weight of 400,000)]
[0125] (5) Presence or absence of inflection point of extensional viscosity (long chain branch structure): The samples were press-molded to prepare test pieces with dimensions of 18 mm x 10 mm and a thickness of 0.7 mm. Using a rheometer (Ares, manufactured by Rheometrics), the extensional viscosity was measured at 170°C and a strain rate of 0.1 / sec. The presence or absence of strain hardening (presence or absence of a rise in extensional viscosity) was used to confirm the presence or absence of a long chain branching structure. [Measurement conditions] Equipment: Rheometrics Ares Fixture: Extentional Viscosity Fixture manufactured by TA Instruments Measurement temperature: 170℃ Strain rate: 0.1 / sec Preparation of test specimens: A sheet of 18 mm x 10 mm and 0.7 mm thick was prepared by press molding. [Calculation method] The extensional viscosity at 170°C and a strain rate of 0.1 / s was plotted on a double logarithmic graph with time t (unit: seconds) on the horizontal axis and extensional viscosity η(t) (unit: Pa·sec) on the vertical axis. On the double logarithmic graph, the maximum extensional viscosity until the strain amount reached 4.0 after strain hardening was η Max (t1) (t1 is the time when the maximum elongational viscosity is shown), and the approximation line of the elongational viscosity before strain hardening is η Linear (t), then η Max (t1) / η Linear The value calculated as (t1) was defined as the degree of strain hardening (λmax). The presence or absence of strain hardening was determined by whether or not there was an inflection point at which the extensional viscosity changed from an upwardly convex curve to a downwardly convex curve with the passage of time.
[0126] (6) Melt tension (MT): The melt tension was determined by measuring the stress when the molten polyethylene resin composition was stretched at a constant speed, and was measured under the following conditions. [Measurement conditions] Machine used: Toyo Seiki Co., Ltd., Capillograph 1B Nozzle diameter: 2.095mm Nozzle length: 8.0mm Inflow angle: 180°(flat) Extrusion speed: 15mm / min Take-up speed: 6.5m / min Measurement temperature: 190℃
[0127] (7) Tensile impact strength (TIS): A 1.5 mm compression molded sheet was prepared in accordance with JIS K6922-2, and a test piece was punched out with an S-shaped dumbbell in accordance with ASTM D1822. Measurements were carried out under conditions of 23°C and 50% RH.
[0128] (8) Environmental stress cracking resistance (FNCT): A circumferential notch creep test was carried out in accordance with ISO DIS 16770. A specimen was prepared by making a 1 mm notch with a razor blade all around the circumference of a 6 mm x 6 mm x 11 mm square column, with a cross section of 4 mm x 4 mm. A tensile stress equivalent to 3.7 MPa was applied to the specimen in pure water at 80°C, and the time until the specimen broke was measured, which was taken as the breakage time of the FNCT.
[0129] (9) Injection stretch blow molding properties: Regarding the cylindrical containers (bottles) with an internal volume of 500 mL that were injection stretch blow molded in the same manner as in the manufacture of the containers described in Example 1, those that could be molded into containers were rated as "good (○)," and those that were damaged (punctured) during stretch blow molding were rated as "poor (×)."
[0130] (10)Impact resistance: Tensile impact strength (TIS) of 130kJ / m 2 If the above conditions were met and the formula (1) was satisfied, the result was marked as "○", otherwise as "×".
[0131] (11) Environmental stress cracking resistance: Those having an environmental stress crack resistance (FNCT) rupture time of 100 hours or more were rated "O", and others were rated "X".
[0132] (12) Mixing (visual inspection of the molded product): The area ratio of fisheyes was measured by the following mixing evaluation method, and the appearance of the molded article was evaluated based on this. [Mixability evaluation method] The sample to be measured is placed in a 0.35 mm thick mold and compressed and cooled using two presses, one for compression and one for cooling. In the first process, the sample is compressed at a temperature of 180°C and a pressure of 100 kgf / cm. 2 In the second step, the mixture is compressed at a temperature of 30°C and a pressure of 50 kgf / cm 2 The mixture was cooled under a pressure of 0.5 to 1000 MPa to form a pressed sheet having a thickness of 0.4 mm. This pressed sheet was cut into test pieces having a size of 50 x 50 x 0.4 mm. Next, the test piece was stretched by a biaxial stretching device. The biaxial stretching device used was a Shibayama Scientific Instruments Manufacturing Co., Ltd. biaxial stretching device SS-60 type, and the test piece was stretched twice at a temperature of 150 ° C. and a stretching speed of 60 mm / min. The stretching procedure was such that 1 cm portions on all four sides of the end of the test piece were chucked with four chucks of the biaxial stretching device, and the unchucked central part of the press sheet was set to be a 30 × 30 mm square. Then, the test piece was heated to a temperature of 130 to 170 ° C. and biaxially stretched until the distance between the diagonal chucks became 60 mm, and a sheet was created in which the unchucked central part was stretched to about 2 times its original size. The surface of the biaxially stretched sheet in a 30×30 mm square area located approximately in the center was imaged using a reflective 3D microscope. The magnification of the 3D microscope was 10 times, and the area of the sheet to be imaged (one field of view) was 10×10 mm. In order to increase the reliability of the measurement, the measurement was performed for one sample four times in a 30×30 mm square area located in the center of the sheet, with each field of view not overlapping. The captured image was binarized into fisheye and non-fisheye areas (uniform matrix areas). The conditions for binarization were set by the person in charge of measurement, and these conditions were used for all measurements. The binarized images were scanned and digitized to produce image data. The resolution of the scanner is 600 dpi or more, and preferably 900 dpi or more. The scanner used was a scanner GT-F670 (manufactured by EPSON, resolution: 4800 dpi). The image data was analyzed using a personal computer and a software program executed on it, and the image data was processed by the personal computer to calculate characteristic parameters such as the area, perimeter, long / short axis ratio, particle size, circularity, etc. The calculation of the characteristic parameters in this case can be performed using commercially available image processing software, and WinROOF manufactured by Mitani Shoji Co., Ltd. was used as the commercially available image analysis software. The image data was binarized and processed at an appropriate level by determining the threshold value of the color scheme of the black and white parts of the image. The conditions of the binarization process were set by the person who performed the measurements, and these conditions were used for all measurements. Image analysis can be performed by known means to calculate the area, perimeter, maximum length, maximum perpendicular length (length in the direction perpendicular to the maximum length), etc. of each particle, and from these, various parameters of the particle can be calculated for each particle. The calculated parameters include the particle's equivalent circle diameter (diameter of a circle with an area equal to the area of the particle's image), circularity (ratio of the perimeter of a circle with an area equal to the area of the particle's image to the perimeter of the image), and aspect ratio (ratio of the maximum length of the particle's image to the maximum perpendicular length). The equivalent circle diameter is calculated by the following formula: equivalent circle diameter = (area value of particle image / π) 1 / 2 ×2, circularity is calculated as follows: circularity = (perimeter of a circle having the area value of the particle image) / (perimeter of the particle image), and aspect ratio is calculated as (maximum length of the particle image) / (maximum vertical length of the particle image). In the present invention, the fisheye area ratio in the image was calculated as the fisheye area ratio for one sample, which was calculated by averaging the measured values obtained in four fields of view photographed on one test piece. The area ratio of fisheyes in the image was then rated as "1" if it was 0.2% or less, "2" if it was between 0.2% and 0.5%, "3" if it was between 0.5% and 3.0%, "4" if it was between 3.0% and 5.0%, and "5" if it was over 5%. If the answer was either "1" or "2", the answer was marked as "○", otherwise it was marked as "×".
[0133] (13)Overall rating: The suitability as a polyethylene resin composition was evaluated, and those which were good in all of the items of injection stretch blow moldability, impact resistance, environmental stress crack resistance, and blending (appearance of molded product) were given an "O" mark, and those which were not good were given an "X" mark.
[0134] 2. Examples and Comparative Examples <Synthesis of metallocene catalyst> In a cylindrical flask equipped with an induction stirrer and thoroughly purged with nitrogen, silica with an average particle size of 11 μm (average particle size 11 μm, surface area 313 m 2 / g, pore volume 1.6 cm 3 3g of 1,1'-{2-(2-(5-methyl)furyl)-4-(p-isopropylphenyl)-indenyl}]zirconium dichloride (63.4mg, 75μmol) in a toluene solution (15mL) was added to the methylalumoxane toluene solution at room temperature, and the mixture was heated to 75°C and stirred for 1 hour. Next, this toluene solution was added to the toluene slurry of silica heated to 75°C while stirring and held for 1 hour. Then, 175mL of n-hexane was added while stirring at 23°C, and after 10 minutes, the stirring was stopped and the mixture was left to stand. After the catalyst was sufficiently settled, the supernatant was removed and 200mL of n-hexane was added. After stirring once, the mixture was again left to stand and the supernatant was removed. This operation was repeated three times to remove the components liberated in n-hexane. The solvent was then distilled off under reduced pressure while heating at 40°C. After the degree of vacuum reached 0.8 mmHg or less, drying under reduced pressure was continued for another 15 minutes to obtain metallocene catalyst (i). <Production of anti-fouling components> In 100 mL of xylene, 3 g of n-octylated polyethyleneimine (0.5 n-octyl groups introduced per monomer unit of polyethyleneimine) derived from polyethyleneimine (molecular weight 10,000) and 1 g of phytic acid, a phosphate ester compound, were mixed and stirred at room temperature to form a salt. Then, 6 g of dioctyl sulfosuccinate magnesium salt was mixed to obtain an anti-fouling component.
[0135] <Production of polyethylene component (A1)> Polyethylene component (A1) was produced by copolymerizing ethylene and 1-hexene with the metallocene catalyst. That is, 115 L / h of dehydrated and purified isobutane, 0.13 mol / h of triisobutylaluminum, and 6 mL / h of antifouling component B were supplied to a loop-type slurry reactor with an internal volume of 290 L. The temperature inside the reactor was set to 80°C, and ethylene, 1-hexene, and hydrogen were supplied while intermittently discharging from the reactor to maintain the pressure at 4.2 MPaG. During polymerization, the molar ratio of 1-hexene to ethylene (C6 / C2) in the liquid was 0.010, and the molar ratio of hydrogen to ethylene (H2 / C2) was 3.4×10 -4 Next, a hexane slurry of catalyst A diluted to 0.3 g / L with hexane was fed to the reactor at 3 L / h to initiate polymerization, and ethylene was fed so that the ethylene concentration in the reactor became 10 vol%. The produced polyethylene was intermittently discharged together with isobutane, and after flashing, it was sent to a product silo. The HLMFR of the polyethylene component (A1) thus obtained was 1.4 g / 10 min and the density was 0.919 g / cm 3 , Mw / Mn was 3.6.
[0136] <Production of polyethylene component (A2)> According to the method for producing the polyethylene component (A1) described above, a polyethylene having an MFR of 3.0 g / 10 min and a density of 0.920 g / cm 3 A polymer with Mw / Mn of 3.7 was produced.
[0137] <Production of polyethylene component (A3)> According to the method for producing the polyethylene component (A1) described above, a polyethylene having an MFR of 0.6 g / 10 min and a density of 0.920 g / cm 3 A polymer with Mw / Mn of 3.1 was produced.
[0138] <Synthesis of Ziegler-Natta catalyst> 20g (17.8mmol) of commercially available magnesium ethylate (average particle size 860μm), 1.64g (12.3mmol) of granular aluminum trichloride, and 2.40g (8.81mmol) of diphenyldiethoxysilane were placed in a pot (grinding vessel) with an internal volume of 1L and containing approximately 700 magnetic balls with a diameter of 10mm, in a nitrogen atmosphere. Next, using a vibrating ball mill, co-grinding was carried out for 3 hours under conditions of an amplitude of 6mm and a vibration frequency of 30Hz. After co-grinding, the contents were separated from the magnetic balls under a nitrogen atmosphere. 10.0 g of the co-ground product obtained as described above and 40 mL of heptane were added to a 200 mL three-neck flask. 10.0 g (52.7 mmol) of titanium tetrachloride was added dropwise at room temperature while stirring, and the mixture was heated to 90°C and stirred for 90 minutes. The reaction system was then cooled, after which the supernatant was removed and hexane was added. This operation was repeated three times. The resulting pale yellow solid was dried at 50°C under reduced pressure for 6 hours to obtain 15.6 g of a solid catalyst. This hexane slurry solution of the solid catalyst was placed in a polymerization reactor equipped with an induction stirrer, the temperature was maintained at 40°C, 0.27 mmol of triisobutylaluminum was added, and prepolymerization was carried out at a hydrogen partial pressure of 0.074 MPa and an ethylene partial pressure of 0.20 MPa, yielding a prepolymerized Ziegler-Natta catalyst with a polymer production of 0.46 g per 1 g of the solid catalyst.
[0139] <Polyethylene component (B1)> Dehydrated and purified isobutane, triisobutylaluminum, the prepolymerized Ziegler-Natta catalyst obtained by the synthesis of the Ziegler-Natta catalyst, and ethylene were continuously fed into a two-tank continuous polymerization apparatus in which two polymerization liquid-filled loop reactors were connected in series, and ethylene was polymerized at 95° C., thereby producing component (B1). The HLMFR of component (B1) was adjusted by feeding an appropriate amount of hydrogen. The polymer has a MFR of 7.5 g / 10 min and a density of 0.963 g / cm 3 , Mw / Mn was 7.4.
[0140] <Polyethylene component (B2)> An ethylene polymer polymerized with a Ziegler-Natta catalyst according to the method for producing the polyethylene component (B1) was used. The ethylene polymer had an MFR of 20 g / 10 min and a density of 0.964 g / cm. 3 , Mw / Mn was 6.0.
[0141] <Polyethylene component (B3)> An ethylene polymer polymerized with a Ziegler-Natta catalyst according to the method for producing the polyethylene component (B1) was used. The ethylene polymer had an MFR of 50 g / 10 min and a density of 0.966 g / cm. 3 , Mw / Mn was 7.4.
[0142] [Example 1] <Production of Polyethylene Resin Composition> A composition having the composition ratio shown in Example 1 in Table 1 was blended with 1,000 ppm of IRGANOX B225 manufactured by BASF Japan Ltd. and 500 ppm of calcium stearate manufactured by Tannan Chemical Industry Co., Ltd. as additives, and pelletized using a TEM26SX manufactured by Toshiba Machine Co., Ltd. (screw diameter: 26 mm, L / D=64) under the conditions of a set temperature of 200°C, a screw rotation speed of 200 rpm, and a discharge rate of 15 kg / hr. The physical properties and evaluation results of the polyethylene resin composition are shown in Table 1. The obtained composition had good compatibility between the components, and due to appropriate fluidity and melt tension, it also had excellent injection stretch blow moldability, a long break time, high tensile impact strength, and a good appearance of the molded product.
[0143] <Container manufacturing> Using the above polyethylene resin composition, a cylindrical parison with a bottom and one end closed (preform) was manufactured by an injection molding machine under conditions of a resin temperature of 250° C. or less, a cavity temperature of the preform molding die of 60° C., and an in-core temperature of 60° C. The preform weighed 30 g, had an overall height of about 120 mm (mouth height about 20 mm, body height about 100 mm), an outer diameter of the mouth about 23 mm, an outer diameter of the body about 25 mm, and a wall thickness of about 3.2 mm. The preform was released from the preform molding die, and the temperature of the preform was lowered below the stretching temperature at one end, and then stretch-blow molding was performed. The temperature of the preform during stretch-blow molding was 128°C, and the temperature of the stretch-blow die was 20°C. The preform was stretched with a stretch rod, and gas was blown into the inside of the preform to mold a container with an internal volume of about 500 mL. The gas was blown into the inside of the preform in two stages, with a primary blow pressure of 0.8 MPa and a secondary blow pressure of 2.5 MPa. The stretch ratio was about 1.8 times in the height direction (axial direction) and about 2.6 times in the width direction (radial direction). After stretch-blow molding, the container had an outer diameter of the mouth of about 23 mm, a height of the mouth of about 20 mm, an outer diameter of the body of about 65 mm, and a height of the body of about 180 mm.
[0144] [Examples 2 to 8, Comparative Examples 1 to 13] A polyethylene resin composition was produced in the same manner as in Example 1, except that the conditions were set so as to obtain the composition shown in Tables 1 and 2. The physical properties and evaluation results of the obtained polyethylene resin composition are shown in Tables 1 and 2.
[0145] [Summary of results] FIG. 3 is a graph showing the relationship between the HLMFR and the tensile impact strength (TIS) of the polyethylene resin compositions of the Examples and Comparative Examples. FIG. 4 is a graph showing the relationship between the HLMFR and the melt tension (MT) of the polyethylene resin compositions of the Examples and Comparative Examples.
[0146] The polyethylene resin compositions of Examples 1 to 8 had good moldability in injection stretch blow molding, and the molded articles had an excellent balance of rigidity, environmental stress crack resistance, and impact resistance, and the resin components had high compatibility, and the molded articles had excellent appearance.
[0147] On the other hand, the polyethylene resin compositions of Comparative Examples 1, 3, 6, 7, 8, 9, 10, 12, and 13, which did not satisfy the property (6), were poor in impact resistance. Moreover, the polyethylene resin compositions of Comparative Examples 1 and 7 were also poor in environmental stress crack resistance. The polyethylene resin compositions of Comparative Examples 2, 4, 5 and 10, which did not satisfy the property (5), were poor in impact resistance. The polyethylene resin compositions of Comparative Examples 6, 7, 8, 9, 10, 11 and 12, which did not use the polyethylene component (A), were inferior in mixing. The polyethylene resin compositions of Comparative Examples 8, 11 and 12, which did not satisfy the characteristic (1), caused punctures in the containers during injection stretch blow molding.
[0148] [Table 1]
[0149] [Table 2] [Industrial Applicability]
[0150] According to the present invention, it is possible to provide a polyethylene resin composition which has good moldability in injection stretch blow molding, high compatibility with resin components, and excellent appearance of molded articles, and a molded article and a container using the same. The polyethylene resin composition of the present invention is excellent in high flowability during molding, and the molded article of the present invention is also excellent in rigidity, environmental stress crack resistance, impact resistance, and the like. Therefore, the polyethylene resin composition of the present invention and a molded article thereof are suitable for applications such as containers which require such properties, and can be particularly suitably used for applications such as cosmetic containers which have excellent appearance, containers for detergents, shampoos and conditioners, or containers for foods such as edible oils. Furthermore, since the polyethylene resin composition of the present invention has excellent performance as described above, it can be suitably used not only for the above-mentioned containers, but also for kerosene cans, chemical containers, and the like which require such properties, and is therefore highly useful industrially.
Claims
1. A polyethylene resin composition comprising, as an essential component, one or more ethylene-based polymers selected from the group consisting of ethylene homopolymers and copolymers of ethylene with an α-olefin having 3 to 12 carbon atoms, containing 15% by mass or more and 40% by mass or less of the following polyethylene component (A), and 60% by mass or more and 85% by mass or less of the following polyethylene component (B), and satisfying the following properties (1) to (8): Polyethylene component (A); Property (a1): Melt flow rate (HLMFR) at a temperature of 190° C. and a load of 21.6 kg is 0.7 g / 10 min or more and 10.0 g / 10 min or less; Property (a2): Density is 0.915 g / cm 3 Above, 0.945g / cm 3 Polyethylene, which is: Polyethylene component (B); Property (b1): Melt flow rate (MFR) at a temperature of 190° C. and a load of 2.16 kg is 5.0 g / 10 min or more and 50.0 g / 10 min or less; Characteristic (b2): Density is 0.950 g / cm 3 Above, 0.980g / cm 3 Polyethylene, which is: Property (1): MFR is greater than 1.0 g / 10 min and less than or equal to 5.0 g / 10 min. Property (2): HLMFR is 30 g / 10 min or more and 300 g / 10 min or less. Property (3): The melt flow rate ratio (HLMFR / MFR), which is the ratio of HLMFR to MFR, is 10 or more and 60 or less. Property (4): Density is 0.940 g / cm 3 Above, 0.965g / cm 3 The following is the result. Property (5): The number average molecular weight (Mn) measured by gel permeation chromatography (GPC) is 8,600 or more, and the weight average molecular weight (Mw) measured by gel permeation chromatography (GPC) is 91,000 or more. Property (6): The branching index calculated by the following formula using the branching numbers per 1,000 carbon atoms of each component at molecular weights of 50,000, 100,000, 200,000, 300,000 and 400,000 as measured by GPC-IR is 2.34 or more. [Branch number index] = [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 50,000] x [X 5万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 100,000] × [X 10万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 200,000] × [X 20万 ] + [Number of branches per 1,000 carbon atoms in a component with a molecular weight of 300,000] × [X 30万 ] + [Number of branches per 1,000 carbon atoms of a component with a molecular weight of 400,000] × [X 40万 ] Where: [X 5万 ] = [weight fraction of molecular weight of 50,000] / [sum of weight fractions of molecular weights of 50,000, 100,000, 200,000, 300,000 and 400,000] [X 10万 ] = [weight fraction of molecular weight 100,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 20万 ] = [weight fraction of molecular weight 200,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000, and 400,000] [X 30万 ] = [weight fraction of molecular weight 300,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000 and 400,000] [X 40万 ] = [weight fraction of molecular weight 400,000] / [sum of weight fractions of molecular weights 50,000, 100,000, 200,000, 300,000 and 400,000] [Sum of weight fractions of molecular weights of 50,000, 100,000, 200,000, 300,000, and 400,000] = [(weight fraction of molecular weight of 50,000) + (weight fraction of molecular weight of 100,000) + (weight fraction of molecular weight of 200,000) + (weight fraction of molecular weight of 300,000) + (weight fraction of molecular weight of 400,000)] Property (7): The tensile impact strength is 130 kJ / m 2 or more. Property (8): The tensile impact strength (TIS) (unit: kJ / m 2 ) and the HLMFR (unit: g / 10 min) satisfy the relationship represented by the following formula (1). TIS≧1560×HLMFR -0.55...Formula (1)
2. A molded article produced using the polyethylene resin composition according to claim 1.
3. A container made using the polyethylene resin composition according to claim 1.
Citation Information
Patent Citations
Ethylene / alpha-olefin copolymer composition
JP1994016880A
Polyethylene-based resin for injection-drawing blow molding
JP1997194534A
Clean polyethylene injection oriented blow molded container
JP1999171923A
High-density polyethylene resin for injection stretch blow molding
JP2000086722A
Polyethylene resin for container cap
JP2005320526A
